Adhesive composition for optical film
Patent Information
- Application Number
- CN202580021278.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-10-15
- Filing Date
- 2025-03-18
- Publication Date
- 2026-10-16
AI Technical Summary
根据本发明,能提供一种即使是厚膜也能形成折射率和透明性得到提高的粘合剂的粘合剂组合物。由该粘合剂组合物形成的粘合剂即使是厚膜,折射率和透明性也得到了提高,因此适合用作光学膜用粘合剂。
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] This invention relates to an adhesive composition for optical films and an adhesive layer. Background Technology
[0002] Image display devices such as liquid crystal displays, organic EL (Electroluminescence) displays, and plasma display panels, as well as optical discs, include optical films such as polarizing plates, retardation plates, optical compensation films, brightness enhancement films, and light diffusion films. A method is known in which a high-refractive-index adhesive is used to bond optical films together or to other components without impairing the functionality of the optical films.
[0003] For example, Patent Document 1 discloses an adhesive composition with a (meth)acrylate polymer as the main component, the (meth)acrylate polymer containing monomers having multiple aromatic rings and monomers having hydroxyl groups as monomer units constituting the polymer.
[0004] Existing technical documents Patent documents Patent Document 1: Japanese Patent Application Publication No. 2017-128732 Summary of the Invention The problem that the invention aims to solve For adhesives formed from the adhesive composition of Patent Document 1, there is a need to further increase the refractive index. A method is known to involve incorporating inorganic particles into the adhesive when further increasing the refractive index. However, the inventors have found that the inorganic particles have poor compatibility with the (meth)acrylate polymer, and even when the resulting adhesive layer has excellent transparency at a thickness of approximately 20 µm, it still fails to exhibit sufficient transparency when used to form a thick film with a thickness of 50 µm or more required for optical film adhesives.
[0005] Therefore, the technical problem of the present invention is to provide an adhesive composition that can form an adhesive with improved refractive index and transparency not only in the case of a thin film, but also in the case of an adhesive layer formed into a thick film.
[0006] Solution for solving the problem In order to solve the aforementioned technical problem, the inventors conducted repeated and in-depth research and discovered that if a specified amount of the same monomer as the monomer constituting the polymer is contained in the form of a monomer in an adhesive composition containing (meth)acrylate polymer and inorganic particles without polymerization, then when the composition is made into a coating film, not only in the case of a thin film, but also in the case of a thick film of 50 µm or more, an adhesive with improved refractive index and transparency can be obtained, thus completing the present invention.
[0007] That is, the present invention is as follows.
[0008] [1] An adhesive composition for optical films is a composition comprising a (meth)acrylate copolymer (A), a (meth)acrylate monomer (a), and inorganic particles (B). The copolymer (A) comprises structural units (A1) derived from an aromatic hydrocarbon-containing (meth)acrylate monomer (a1) and structural units (A2) derived from a hydroxyl-containing (meth)acrylate monomer (a2). The monomer (a) comprises an aromatic hydrocarbon-containing (meth)acrylate monomer (a1) and a hydroxyl-containing (meth)acrylate monomer (a2). The content of the structural unit (A2) is 1-40% by mass of 100% by mass of the copolymer (A). The content of the monomer (a) is 45 to 95% by mass of the total 100% mass of the copolymer (A) and the monomer (a).
[0009] [2] According to the adhesive composition described in [1], the adhesive composition further contains a photopolymerization initiator (E).
[0010] [3] According to the adhesive composition of [1] or [2], wherein the monomer (a1) is at least one selected from the group consisting of aryl esters of (meth)acrylic acid, aralkyl esters of (meth)acrylic acid, and aryloxyalkyl esters of (meth)acrylic acid. The aryl esters, aralkyl esters, and aryloxyalkyl esters of (meth)acrylic acid are optionally bonded with aryl, aralkyl, aroxy, or aroxyalkyl groups. The aryl esters, aralkyl esters, and aryloxyalkyl esters of (meth)acrylic acid are optionally epoxide-modified.
[0011] [4] According to any one of [1] to [3], the adhesive composition wherein the copolymer (A) comprises structural units (A3) derived from monomers other than aromatic hydrocarbon-containing (meth)acrylate monomers (a1) and hydroxyl-containing (meth)acrylate monomers (a2). The (meth)acrylate monomer (a) comprises monomers (a3) other than the (meth)acrylate monomer (a1) containing an aromatic hydrocarbon group and the (meth)acrylate monomer (a2) containing a hydroxyl group. The content of the structural unit (A3) is less than 50% by mass of 100% by mass of the copolymer (A).
[0012] [5] According to the adhesive composition of [4], wherein the other monomer (a3) comprises at least one selected from the group consisting of alicyclic hydrocarbon monomers, nitrogen-containing monomers, alkoxyalkyl monomers, low Tg alkyl methacrylate monomers with a glass transition temperature of less than -20°C for the homopolymer, and monomers containing acid groups.
[0013] [6] The adhesive composition according to any one of [1] to [5], wherein the copolymer (A) has a weight-average molecular weight of 500,000 to 6,000,000.
[0014] [7] The adhesive composition according to any one of [1] to [6], wherein the inorganic particles (B) are particles composed of at least one selected from the group consisting of alumina, titanium oxide, zirconium oxide, indium oxide, zinc oxide, tin oxide, lanthanum oxide, yttrium oxide, cerium oxide, magnesium oxide, niobium oxide, tantalum oxide, indium tin oxide, antimony tin oxide, barium titanate, strontium titanate, perovskite and spinel.
[0015] [8] The adhesive composition according to any one of [1] to [7], wherein the volume average particle size of the inorganic particles (B) is 1 to 100 nm.
[0016] [9] The adhesive composition according to any one of [1] to [8], wherein the ratio (D90 / D50) of the cumulative 90% particle size D90 of the volume reference to the cumulative 50% particle size D50 of the volume reference in the particle size determination of the inorganic particles (B) based on dynamic light scattering method is 3.0 or less.
[0017] [10] The adhesive composition according to any one of [1] to [9], wherein the adhesive composition further contains a chain transfer agent (F).
[0018] [11] The adhesive composition according to any one of [1] to
[10] , wherein the refractive index of the adhesive layer formed by the adhesive composition is 1.58 to 1.80.
[0019] [12] The adhesive composition according to any one of [1] to
[11] , wherein the haze of the adhesive layer with a thickness of 100µm formed by the adhesive composition is 3.0% or less.
[0020] [13] An adhesive layer formed from an adhesive composition according to any one of [1] to
[12] .
[0021] [14] Use of a composition in an adhesive laminated on an optical film, said composition being any one of [1] to
[12] .
[0022] [15] A laminate comprising an optical film and an adhesive layer according to
[13] laminated on the optical film.
[0023] [16] A method for manufacturing an optical film laminated with an adhesive, comprising: The process of applying the composition according to any one of [1] to
[12] to a substrate; and The process of curing the coating layer obtained in the coating process to form an adhesive layer. The substrate used in the coating process is an optical film, or the process may further include a transfer process after the adhesive layer formation process to transfer the adhesive layer to the optical film.
[0024] [17] An adhesive layer comprising an (meth)acrylate copolymer (A) and inorganic particles (B) for use in optical films. The thickness of the adhesive layer is 50µm or more. The haze of the adhesive layer is below 3.0%. The copolymer (A) comprises structural units (A1) derived from an aromatic hydrocarbon-containing (meth)acrylate monomer (a1) and structural units (A2) derived from a hydroxyl-containing (meth)acrylate monomer (a2). The content of the structural unit (A2) is 1 to 40% of the total 100% mass of structural units (A1) and (A2).
[0025] [18] The adhesive layer according to
[17] contains photopolymerization initiator residue.
[0026] Invention Effects According to the present invention, an adhesive composition is provided that can form an adhesive with improved refractive index and transparency even in thick films. The adhesive formed from this adhesive composition exhibits improved refractive index and transparency even in thick films, and is therefore suitable for use as an adhesive for optical films. Detailed Implementation
[0027] 1. Adhesive composition The adhesive composition of the present invention is preferably used for optical films, comprising a (meth)acrylate copolymer (A) (hereinafter, sometimes simply referred to as copolymer (A)), a (meth)acrylate monomer (a) (hereinafter, sometimes simply referred to as monomer (a)), and inorganic particles (B). By including copolymer (A), adhesiveness is achieved; by including inorganic particles (B), the refractive index of the adhesive layer is increased, making it suitable for bonding (adhesive bonding) of optical films. Furthermore, although the inclusion of inorganic particles (B) generally tends to reduce transparency, this adhesive composition, by including monomer (a), improves the dispersibility of inorganic particles (B) in the adhesive composition. Therefore, even after reducing the proportion of monomer (a) after coating the adhesive composition and allowing the adhesive composition to cure, high dispersibility is maintained, and the transparency of the adhesive layer is improved.
[0028] 1.1 (Meth)acrylate copolymer (A) The (meth)acrylate copolymer (A) comprises structural units (A1) derived from an aromatic hydrocarbon-containing (meth)acrylate monomer (a1) (hereinafter, sometimes simply referred to as aromatic monomer (a1) or monomer (a1)) and structural units (A2) derived from a hydroxyl-containing (meth)acrylate monomer (a2) (hereinafter, sometimes simply referred to as hydroxyl-containing monomer (a2) or monomer (a2)). The inclusion of the aromatic structural unit (A1) increases the refractive index of the adhesive layer, making it suitable for use in optical films. Furthermore, it reduces the refractive index difference with the inorganic particles (B), contributing to improved transparency of the adhesive layer. The inclusion of the hydroxyl-containing structural unit (A2) increases the affinity with the inorganic particles (B). Additionally, it reduces the formation of water droplets in the adhesive layer under humidified conditions, also improving transparency under humidified conditions.
[0029] 1.1.1 Aromatic structural unit (A1) The aromatic monomer (a1) that becomes the aromatic structural unit (A1) is preferably a monomer having an aromatic hydrocarbon ring (sometimes called an aryl unit) and a (meth)acryloyl group within its molecule. Examples of aromatic monomers (a1) include aryl esters of (meth)acrylic acid, aralkyl esters of (meth)acrylic acid (i.e., arylalkyl esters of (meth)acrylic acid), and aryloxyalkyl esters of (meth)acrylic acid, which can be used alone or in combination of two or more.
[0030] It should be noted that the aryl esters, aralkyl esters, and aryloxyalkyl esters of (meth)acrylic acid are optionally bonded with aromatic substituents having an aromatic hydrocarbon ring, such as aryl, aralkyl, aroxy, or aroxyalkyl groups.
[0031] Furthermore, the aryl esters, aralkyl esters, and aryloxyalkyl esters of (meth)acrylic acid can be epoxide-modified products.
[0032] The aryl units contained in the aryl methacrylate, arylalkyl methacrylate (i.e., arylalkyl ester), aryloxyalkyl methacrylate, aryl, aryl, aryloxy, and aryloxyalkyl esters include benzene ring units, naphthyl ring units, azurite ring units, anthracene ring units, phenanthrene ring units, pyrene ring units, cyclopentadiene ring units, tetraphenylbenzene ring units, triphenylene ring units, fluorene ring units, dinaphthothiophene ring units, etc., preferably benzene ring units, naphthyl ring units, fluorene ring units, etc. Furthermore, by bonding aromatic substituents such as aryl, arylalkyl, aryloxy, and aryloxyalkyl groups to the aryl methacrylate, arylalkyl methacrylate (i.e., arylalkyl ester), or aryloxyalkyl methacrylate, groups containing multiple aryl groups can be formed. Examples of such groups containing multiple aryl groups include biphenylcycloyl, phenoxybenzyl, ortho-terphenylcycloyl, meta-terphenylcycloyl, and para-terphenylcycloyl.
[0033] The alkyl units contained in the arylalkyl esters (i.e., arylalkyl esters), aryloxyalkyl esters (meth)acrylates, arylalkyl and aryloxyalkyl esters, etc., contain alkyl units with 1 to 10 carbon atoms, preferably containing 1 to 4 carbon atoms, more preferably containing 1 to 2 carbon atoms.
[0034] The epoxides include ethylene oxide, propylene oxide, etc., with ethylene oxide being preferred.
[0035] As aromatic monomers (a1), specifically, examples include: benzyl (meth)acrylate, phenyl (meth)acrylate, benzyl phenyl (meth)acrylate, p-phenyl benzyl (meth)acrylate, o-phenylphenol (meth)acrylate, ethoxylated o-phenylphenol (meth)acrylate, phenoxy acrylate, p-tert-butyl phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxypropyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, and ethylene glycol with 3 repeating units. The following are examples of phenoxy polyethylene glycol (meth)acrylate, ethylene oxide modified nonylphenol (meth)acrylate, nonylphenoxy polyethylene glycol (meth)acrylate, nonylphenoxy polyethylene glycol-polypropylene glycol (meth)acrylate, ethylene oxide modified cresol (meth)acrylate, phenol ethylene oxide modified (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, methoxybenzyl (meth)acrylate, m-phenoxybenzyl (meth)acrylate, and (meth)acrylate (preferably 3 to 20%). Monomers containing benzyl chloride, cresolyl (meth)acrylate, polystyrene (meth)acrylate, 2-(meth)acryloyloxyethyl-2-hydroxyethyl phthalate, monohydroxyethyl (meth)acrylate, etc.; hydroxyethylated β-naphthol (meth)acrylate, 2-naphthyl ethyl (meth)acrylate, 2-naphthyloxyethyl (meth)acrylate, 2-(4-methoxy-1-naphthyloxy)ethyl (meth)acrylate, 1-naphthyl methyl (meth)acrylate, 2-naphthyl (meth)acrylate Monomers containing a naphthyl ring unit, such as methyl methacrylate and hydroxynaphthyl methacrylate; monomers containing a biphenyl ring group, such as biphenyl methacrylate; monomers containing a fluorenyl group, such as fluorenyl methacrylate, 9-fluorenyl methacrylate (9-(meth)acryloyloxymethylfluoren), and hydroxyfluorenyl methacrylate; monomers containing a dinaphthiophene ring unit, such as 5-dinaphthiophene ethyl methacrylate, 6-dinaphthiophene ethyl methacrylate, and 6-dinaphthiophene methyl methacrylate. Monomer (a1) preferably does not have a carboxyl group, a phosphate group, a phosphate ester group, a sulfonic acid group, or a sulfonate ester group.
[0036] In addition, as monomers (a1), commercially available products such as M-101A, M-102, M-111, M-113, M-5400, and M-5700 manufactured by Toa Synthetic Co., Ltd.; Blemmer ANP-300 and 75ANEP-600 manufactured by Nippon Oil Co., Ltd.; and NK Ester AMP-20GY manufactured by Shin-Nakamura Chemical Industry Co., Ltd. can also be used.
[0037] Preferred aromatic monomers (a1) include aralkyl esters of (meth)acrylic acid (e.g., benzyl (meth)acrylic acid, naphthyl methyl (meth)acrylic acid, etc.), or aromatic monomers with aromatic substituents (preferably aryl or aryloxy) bonded to the aralkyl ester of (meth)acrylic acid (e.g., p-phenyl benzyl acrylate, phenoxy benzyl acrylate, etc.), aryloxyalkyl esters of (meth)acrylic acid (e.g., phenoxyethyl (meth)acrylic acid, etc.), and aromatic monomers with aromatic substituents (preferably aryl) bonded to the aryloxyalkyl ester of (meth)acrylic acid (e.g., ethoxylated o-phenylphenol (meth)acrylic acid, etc.).
[0038] In particular, as an aromatic monomer (a1). Preferably, it comprises an aromatic monomer bonded with an aromatic substituent (preferably aryl or aryloxy) to an aralkyl ester of (meth)acrylic acid, and / or an aryloxyalkyl ester of (meth)acrylic acid. More preferably, it is an aromatic monomer containing at least an aralkyl ester of (meth)acrylic acid bonded with an aromatic substituent (preferably aryl or aryloxy). Further preferred are aromatic monomers containing an aromatic monomer bonded with an aromatic substituent (preferably aryl or aryloxy) group and an aryloxyalkyl ester of (meth)acrylic acid.
[0039] As an aralkyl ester of the (meth)acrylic acid, C(meth)acrylic acid is preferred. 6-10 Aryl C 1-4 Alkyl ester, more preferably (meth)acrylate phenyl C 1-4 Alkyl ester, (meth)acrylate naphthyl C 1-4 Alkyl esters.
[0040] As an aromatic monomer having aromatic substituents bonded to the aralkyl ester of (meth)acrylic acid, in the preferred embodiment of the above-mentioned aralkyl ester of (meth)acrylic acid (i.e., (meth)acrylic acid C... 6-10 Aryl C 1-4 Alkyl esters, (meth)acrylate phenyl C 1-4 Alkyl esters or (meth)acrylate naphthyl C 1-4 In alkyl esters, aromatic monomers bonded with aryl or aryloxy groups (especially aryloxy groups) are preferred. In the preferred embodiments of the above-mentioned aryl esters of (meth)acrylic acid, aromatic monomers bonded with phenyl or phenoxy groups (especially phenoxy groups) are more preferred.
[0041] As an aryloxyalkyl ester of the (meth)acrylic acid, C4-(meth)acrylic acid is preferred. 6-10 Aryloxy C 1-4 Alkyl esters, more preferably phenoxy C of (meth)acrylic acid 1-4Alkyl esters.
[0042] As an aromatic monomer having aromatic substituents bonded to the aryloxyalkyl ester of (meth)acrylic acid, in the preferred embodiment of the above-mentioned aryloxyalkyl ester of (meth)acrylic acid (i.e., C4 of (meth)acrylic acid) 6-10 Aryloxy C 1-4 alkyl esters or phenoxy C of (meth)acrylic acid 1-4 In the alkyl ester, an aromatic monomer bonded with an aryl group or its alkyl oxide modified form is preferred. In the preferred embodiment of the above-mentioned aryloxyalkyl ester of (meth)acrylic acid, an aromatic monomer bonded with an aryl group or its ethylene oxide or propylene oxide modified form is more preferred. In the preferred embodiment of the above-mentioned aryloxyalkyl ester of (meth)acrylic acid, an aromatic monomer bonded with a phenyl group or its ethylene oxide or propylene oxide modified form is even more preferred.
[0043] The content of aromatic structural units (A1) in 100% by mass of copolymer (A) is, for example, 40-99% by mass, preferably 50-95% by mass, and more preferably 70-90% by mass. The higher the content of aromatic structural units (A1), the higher the refractive index of the adhesive layer. In addition, the transparency of the adhesive layer is also easily improved.
[0044] It should be noted that the proportions of the structural units ((A1) and (A2), (A3), etc., as described later) in copolymer (A) can be determined by separating the monomer (a) in the adhesive composition from copolymer (A) using solid-liquid separation, extraction, etc., and then analyzing copolymer (A) using NMR, etc. Furthermore, if it is known that the proportions of monomers (a1), (a2), and (a3) (specifically (a31) to (a42)) at the charge during polymerization are equal to the proportions of the structural units (A1), (A2), and (A3) (specifically (A31) to (A42)) in copolymer (A), the proportions of the structural units (A1), (A2), and (A3) (specifically (A31) to (A42)) in copolymer (A) can be determined based on the charge ratio instead of analysis.
[0045] 1.1.2 Hydroxyl-containing structural unit (A2) The hydroxyl-containing monomer (a2) that forms the hydroxyl-containing structural unit (A2) is preferably a monomer having an intramolecular hydroxyl group and a (meth)acryloyl group (wherein, it does not have an aromatic hydrocarbon ring). Examples of hydroxyl-containing monomers (a2) include: 4-hydroxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, hydroxymethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, etc. (meth)acrylate hydroxy C 1-10Alkyl esters; polyethylene glycol mono(meth)acrylates with 2 or more repeating units (preferably 2 or more and 20 or less), and polypropylene glycol mono(meth)acrylates with 2 or more repeating units (preferably 2 or more and 20 or less), etc. 2-4 Alkylene glycol mono(meth)acrylate; (meth)acrylate hydroxyl C 1-10 Alkyl esters modified with caprolactone; methacrylates containing hydroxyl groups and aliphatic hydrocarbon rings, such as 1,4-cyclohexanediethanol mono(meth)acrylate; and methacrylamides such as N-(2-hydroxyethyl)(meth)acrylamide, N-(2-hydroxypropyl)(meth)acrylamide, and N-(2,2-dimethyl-β-hydroxyethyl)(meth)acrylamide. Furthermore, as monomers (a2), commercially available products such as PLACEL FA1, FA1DDM, FA2, FA2D, FA3, FA4, FA5, FA10L, FM1, FM1D, FM2, FM2D, FM3, FM4, and FM5 manufactured by Daicel Corporation, and BLEMMER AE-90U, AE-200, AE-400, AP-200, AP-400, AP-400D, AP-550, AP-800, and AP-1000D manufactured by Nippon Oil Co., Ltd., can also be used. These hydroxyl-containing monomers (a2) can be used alone or in combination of two or more.
[0046] Among these, considering good transparency, low gel content in copolymer (A), and good appearance, (meth)acrylic acid hydroxy C is preferred. 2-4 Alkyl esters, N-(hydroxyl C) 2-4 Alkyl (meth)acrylamide, PLACEL (especially the F series) manufactured by Daicel Corporation, and more preferably 4-hydroxybutyl (meth)acrylate, N-(2-hydroxyethyl) (meth)acrylamide, PLACEL FA1DDM, FA2D, FM1D, FM2D, and FM5. Furthermore, from the viewpoint of further improving transparency, hydroxyl C (meth)acrylate is preferred. 1-10 Alkyl esters, more preferably (meth)acrylic acid hydroxy C 2-4 Alkyl esters.
[0047] The content of the hydroxyl-containing structural unit (A2) in 100% by mass of the copolymer (preferably in 100% by mass of the total of structural units (A1) and (A2), is, for example, 1 to 40% by mass, preferably 3 to 30% by mass, more preferably 7 to 25% by mass, and may also be 12 to 25% by mass. A higher content of the hydroxyl-containing structural unit (A2) further enhances the affinity with the inorganic particles (B) and also further improves transparency under humidified conditions. Furthermore, a lower content of the hydroxyl-containing structural unit (A2) improves the hygrothermal durability of the adhesive composition and enhances its adhesion and coatability.
[0048] The total content of aromatic structural units (A1) and hydroxyl-containing structural units (A2) in 100% by mass of copolymer (A) is, for example, 50-100% by mass, preferably 60-99% by mass, more preferably 75-95% by mass, and may also be 85-100% by mass or 95-100% by mass. Furthermore, the mass ratio (A1 / A2) of aromatic structural units (A1) to hydroxyl-containing structural units (A2) is, for example, 50 / 50-99 / 1, preferably 70 / 30-98 / 2, more preferably 75 / 25-95 / 5, even more preferably 80 / 20-90 / 10, and particularly preferably 83 / 17-88 / 12.
[0049] 1.1.3 Other structural units (A3) The copolymer (A) may also contain structural units (A3) derived from monomers other than aromatic monomers (a1) and hydroxyl-containing monomers (a2) (hereinafter, sometimes referred to as other structural units (A3) or structural units (A3)). By including other structural units (A3), various properties can be acquired by the copolymer (A).
[0050] The content of other structural units (A3) in 100% by mass of copolymer (A) is, for example, 0 to 50% by mass, preferably 1 to 50% by mass, more preferably 1 to 40% by mass, and even more preferably 5 to 25% by mass.
[0051] Other monomers (a3) that can become other structural units (A3) include: (meth)acrylate monomers containing alicyclic hydrocarbon groups (a31), (meth)acrylate monomers containing nitrogen atoms (a32), (meth)acrylate monomers containing alkoxyalkyl groups (a33), low-Tg (meth)acrylate alkyl monomers with a glass transition temperature below -20°C in homopolymers (a34), (meth)acrylate alkyl monomers with a glass transition temperature above -20°C in homopolymers (a35), monomers containing acid groups (a36), and (meth)acrylate monomers having acyl or cyclic ether groups (especially epoxy groups) (a3). 7) Monomers containing phosphate groups (a38), monomers containing sulfonic acid groups (a39), vinyl monomers containing silane groups (a40), styrene monomers (a41), macromolecular monomers (a42), etc., preferably monomers (a31) to (a40), more preferably (a31) monomers containing alicyclic hydrocarbon groups (a31), (a32) monomers containing nitrogen atoms (a32), (a33) monomers containing alkoxyalkyl groups (a33), low Tg (a34) alkyl (a34) monomers with a glass transition temperature of -20°C or less for homopolymers, monomers containing acid groups (a36), etc. These other monomers (a3) can be used alone or in combination of two or more. When using (a31) monomers containing alicyclic hydrocarbon groups, the dielectric constant of the adhesive layer can be reduced. When nitrogen-containing (meth)acrylate monomers (a32) are used, hydrophilicity is improved, cloudiness of the adhesive layer under humidified conditions is suppressed, and cohesion is enhanced, thereby increasing the adhesive strength of the adhesive layer. When alkoxyalkyl (meth)acrylate monomers (a33) are used, hydrophilicity of the adhesive layer is improved, and cohesion is enhanced, thereby increasing the adhesive strength of the adhesive layer. When low-Tg (meth)acrylate alkyl monomers (a34) with a glass transition temperature below -20°C of the homopolymer are used, adhesion is improved, thereby increasing the adhesive strength of the adhesive layer. When acid-containing monomers (a36) are used, cohesion is improved, thereby increasing the adhesive strength of the adhesive layer.
[0052] It should be noted that the structural unit derived from the monomer (a31) is called structural unit (A31), and similarly, the structural units derived from the monomers (a32) to (a42) are called structural units (A32) to (A42), respectively.
[0053] The (meth)acrylate monomer (a31) containing an alicyclic hydrocarbon group (sometimes simply referred to as monomer (a31)) is preferably a monomer having an alicyclic hydrocarbon ring and a (meth)acryloyl group (wherein, it does not have an aromatic hydrocarbon ring and a hydroxyl group). Examples of monomers (a31) include: monocyclic monomers represented by cycloalkyl methacrylates such as cyclopentyl methacrylate, cyclohexyl methacrylate, and 3,3,5-trimethylcyclohexyl methacrylate; and bridged ring monomers such as isobornyl methacrylate, dicyclopentyl methacrylate, dicyclopentenyl methacrylate, adamantyl methacrylate, and dicyclopentenoxyethyl methacrylate, with isobornyl methacrylate being the most preferred. In addition, commercially available products such as FANCRYL FA-511AS, FA-512AS, and FA-513AS manufactured by Resonac Co., Ltd. can also be used as monomers (a31).
[0054] The content of structural unit (A31) derived from the monomer (a31) is, for example, 0 to 50% by mass in 100% by mass of copolymer (A), preferably 5 to 40% by mass, and more preferably 10 to 30% by mass.
[0055] Nitrogen-containing (meth)acrylate monomers (a32) (sometimes simply referred to as monomers (a32)) are preferably monomers that have a nitrogen atom and a (meth)acryloyl group (wherein, they do not have an aromatic hydrocarbon ring and a hydroxyl group). Examples of monomers (a32) include: amino-containing monomers such as dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, N-tert-butylaminoethyl (meth)acrylate, and methacryloyloxyethyltrimethylammonium chloride; monomers containing amide groups such as N-(meth)acryloylmorpholine, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, (meth)acrylamide, N-isopropyl(meth)acrylamide, N-tert-butyl(meth)acrylamide, and diacetone(meth)acrylamide; monomers with urethane (meth)acrylate groups such as urethane esters; and monomers containing imide groups such as N-(meth)acryloyloxyethylhexahydrophthalimide, with amide-containing monomers such as N-acryloylmorpholine being preferred. Furthermore, commercially available products such as M-140 manufactured by Toa Synthetic Co., Ltd. can also be used as monomers (a32). It should be noted that in this specification, monomers having a nitrogen atom, (meth)acryloyloxy group and alicyclic hydrocarbon ring (wherein, there is no aromatic hydrocarbon ring and hydroxyl group) are classified as monomers (a32).
[0056] The content of structural unit (A32) derived from the monomer (a32) is, for example, 0 to 50% by mass in 100% by mass of copolymer (A), preferably 1 to 30% by mass, and more preferably 5 to 20% by mass.
[0057] Alkoxyalkyl (meth)acrylate monomers (a33) (sometimes simply referred to as monomer (a33)) are preferably monomers having an alkoxyalkyl group and a (meth)acryloyl group (wherein, they do not have an aromatic hydrocarbon ring and a hydroxyl group) within the molecule. Examples of monomers (a33) include, for example, methoxyethyl (meth)acrylate, ethoxymethyl (meth)acrylate, ethoxyethyl (meth)acrylate, propoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, methoxypropyl (meth)acrylate, methoxybutyl (meth)acrylate, 2-ethylhexyloxyethyl (meth)acrylate, and other alkoxyalkyl (meth)acrylate esters (preferably C-meth)acrylate. 1-4 Alkoxy C 1-4 Alkyl esters); ethoxy-diethylene glycol (meth)acrylate, ethoxy-triethylene glycol (meth)acrylate, methoxy-triethylene glycol (meth)acrylate, methoxy-diethylene glycol (meth)acrylate, propoxy-diethylene glycol (meth)acrylate, propoxy-triethylene glycol (meth)acrylate, 2-ethylhexyl-diethylene glycol (meth)acrylate (2-ethylhexyloxy-diethylene glycol (meth)acrylate), 2-ethylhexyloxy-triethylene glycol (meth)acrylate, 2-ethylhexyloxy-polyethylene glycol (meth)acrylate with 4 or more repeating units of ethylene glycol (preferably 4 or more and 10 or less), methoxy-polyethylene glycol (meth)acrylate with 4 or more repeating units of ethylene glycol (preferably 4 or more and 25 or less, more preferably 4 or more and 10 or less), methoxy-dipropylene glycol (meth)acrylate, etc. C 1-8 Alkoxy (poly) C 2-4 Alkyl glycol (meth)acrylates, etc.; preferably (meth)acrylate methoxyethyl esters, etc. (meth)acrylate C 1-4 Alkoxy C 1-4 Alkyl esters. In addition, as monomers (a33), commercially available products such as M-120 manufactured by Toa Synthetic Co., Ltd.; BLEMMER AME-400 manufactured by Nippon Oil Co., Ltd.; and NKEster AM-90G, AM-130G, and AM-230G manufactured by Shin-Nakamura Chemical Industry Co., Ltd. can also be used.
[0058] The content of structural unit (A33) derived from the monomer (a33) is, for example, 0 to 50% by mass in 100% by mass of copolymer (A), preferably 5 to 40% by mass, and more preferably 10 to 30% by mass.
[0059] For low-Tg (meth)acrylate alkyl ester monomers (a34) (sometimes simply referred to as monomer (a34)) with a glass transition temperature below -20°C and (meth)acrylate alkyl ester monomers (a35) (sometimes simply referred to as monomer (a35)) with a glass transition temperature above -20°C, the following examples of monomers with corresponding glass transition temperatures can be listed: methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, and so on. Amyl acrylate, isoamyl acrylate, 2-ethylhexyl acrylate, hexyl acrylate, heptyl acrylate, octyl acrylate, 2-octyl acrylate, 2-ethylhexyl acrylate, nonyl acrylate, isononyl acrylate, decyl acrylate, isodecyl acrylate, dodecyl acrylate (lauryl acrylate), stearyl acrylate, isostearyl acrylate, cetyl acrylate, behenyl acrylate.
[0060] In addition, as monomers (a34) and (a35), commercially available products such as BLEMMER CA and VA manufactured by Nippon Oil Co., Ltd., and FANCRYL FA-111A manufactured by Resonac Co., Ltd. can also be used.
[0061] As the monomer (a34), ethyl acrylate, n-propyl acrylate, n-butyl acrylate, isobutyl acrylate, n-pentyl acrylate, n-hexyl acrylate, n-octyl acrylate, 2-octyl acrylate, 2-ethylhexyl acrylate, n-nonyl acrylate, isononyl acrylate, etc., are preferred, and n-butyl acrylate and 2-ethylhexyl acrylate are more preferred.
[0062] The content of the structural unit (A34) derived from the monomer (a34) is, for example, 0 to 50% by mass in 100% by mass of the copolymer (A), preferably 0 to 30% by mass, and more preferably 1 to 20% by mass.
[0063] The content of the structural unit (A35) derived from the monomer (a35) is, for example, 0 to 50% by mass in 100% by mass of the copolymer (A), preferably 0 to 10% by mass, and more preferably 0 to 5% by mass.
[0064] The monomer containing an acid group (a36) (sometimes simply referred to as monomer (a36)) is preferably a monomer with a carboxyl group and a polymerizable unsaturated group (wherein, it does not have an aromatic hydrocarbon ring and a hydroxyl group) in the molecule. Examples of monomers (a36) include: unsaturated monocarboxylic acids such as (meth)acrylic acid, cinnamic acid, crotonic acid, myristoleic acid, palmitoleic acid, and oleic acid; unsaturated dicarboxylic acids such as maleic acid, fumaric acid, itconic acid, and citralic acid; monoesters of unsaturated dicarboxylic acids such as monomethyl maleate, monobutyl maleate, monomethyl itconic acid, and monobutyl itconic acid; anhydrides of unsaturated dicarboxylic acids such as maleic anhydride, fumaric anhydride, and itconic anhydride; saturated dicarboxylic acid monoesters with polymerizable unsaturated groups in the ester portion, such as 2-(meth)acryloyloxyethyl succinate and 2-(meth)acryloyloxyethyl hexahydrophthalic acid; and ω-carboxyl-polycaprolactone mono(meth)acrylate, preferably unsaturated monocarboxylic acids, and more preferably (meth)acrylic acid. In addition, commercially available products such as M-5300 manufactured by Toa Synthetic Co., Ltd. and NK Ester A-SA manufactured by Shin-Nakamura Chemical Co., Ltd. can also be used as monomers (a36). It should be noted that in this specification, monomers having a carboxyl group, a polymerizable unsaturated group, and an alicyclic hydrocarbon ring (wherein, there is no aromatic hydrocarbon ring and hydroxyl group) are classified as monomers (a36).
[0065] The content of the structural unit (A36) derived from the monomer (a36) is, for example, 0 to 50% by mass in 100% by mass of the copolymer (A), preferably 0 to 30% by mass, more preferably 0 to 10% by mass, or may be 0% by mass (i.e., acid-free).
[0066] (Meth)acrylate monomers (a37) having an acyl or cyclic ether group (sometimes simply referred to as monomer (a37)) are preferably monomers having an acyl and / or cyclic ether group and a (meth)acryloyl group (wherein, without an aromatic hydrocarbon ring and a hydroxyl group). Examples of the cyclic ether group include: epoxy, oxetyl, tetrahydrofuranyl, and other cyclic ether groups having one ether bond; 1,3-dioxacyclopentyl... Cyclic ether groups having two ether bonds, such as 1,3-dioxanehexyl groups, are preferred, especially epoxy groups. That is, the monomer (a37) is preferably a (meth)acrylate monomer having an acyl or epoxy group. Examples of monomers (a37) include: glycidyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate glycidyl ether, tetrahydrofurfuryl (meth)acrylate, cyclic trimethylolpropane acetal (meth)acrylate, (2-methyl-2-ethyl-1,3-dioxane-4-yl)methyl (meth)acrylate, (3-ethyloxecyclobutane-3-yl)methyl (meth)acrylate, and 2-acetylacetoxyethyl (meth)acrylate.
[0067] The content of the structural unit (A37) derived from the monomer (a37) is, for example, 0 to 50% by mass in 100% by mass of the copolymer (A), preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.
[0068] The (meth)acrylic monomer (a38) having a phosphate group (sometimes simply referred to as monomer (a38)) is preferably a monomer having a phosphate group and / or a phosphate ester group and a polymerizable unsaturated group (wherein, it does not have an aromatic hydrocarbon ring and a hydroxyl group). Examples of monomers (a38) include, for example, 2-methacryloyloxyethyl diphenyl phosphate (meth)acrylate, trimethacryloyloxyethyl phosphate (meth)acrylate, and triacryloyloxyethyl phosphate (meth)acrylate.
[0069] The content of the structural unit (A38) derived from the monomer (a38) is, for example, 0 to 50% by mass in 100% by mass of the copolymer (A), preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.
[0070] The monomer containing a sulfonic acid group (a39) (sometimes simply referred to as monomer (a39)) is preferably a monomer having a sulfonic acid group and / or a sulfonate group and a polymerizable unsaturated group (wherein, it does not have an aromatic hydrocarbon ring and a hydroxyl group) within its molecule. Examples of monomers (a39) include sodium sulfopropyl (meth)acrylate, sodium 2-sulfoethyl (meth)acrylate, sodium 2-acrylamide-2-methylpropanesulfonate, etc.
[0071] The content of structural unit (A39) derived from the monomer (a39) is, for example, 0 to 50% by mass in 100% by mass of copolymer (A), preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.
[0072] The vinyl monomer (a40) having a silane group (sometimes simply referred to as monomer (a40)) is preferably a monomer having a silane group and a vinyl group (wherein, it does not have an aromatic hydrocarbon ring and a hydroxyl group) within its molecule. Examples of monomers (a40) include vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(β-methoxyethyl)silane, vinyltriacetylsilane, methacryloxypropyltrimethoxysilane, etc. It should be noted that, in this specification, monomers having a silane group, a vinyl group, and an acyl group (wherein, it does not have an aromatic hydrocarbon ring and a hydroxyl group) within their molecule are classified as monomers (a40).
[0073] The content of structural unit (A40) derived from the monomer (a40) is, for example, 0 to 50% by mass in 100% by mass of copolymer (A), preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.
[0074] Styrene-based monomers (a41) (sometimes simply referred to as monomers (a41)) are preferably monomers having a styrene skeleton (wherein, they do not have hydroxyl groups). Examples of monomers (a41) include styrene, 4-tert-butylstyrene, α-methylstyrene, m-methylstyrene, p-methylstyrene, p-chlorostyrene, p-chloromethylstyrene, etc.
[0075] The content of the structural unit (A41) derived from the monomer (a41) is, for example, 0 to 50% by mass in 100% by mass of the copolymer (A), preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.
[0076] Macromonomer (a42) (sometimes simply referred to as monomer (a42)) refers to a high-quantity monomer with polymerizable unsaturated groups. The number-average molecular weight of monomer (a42) is not particularly limited, for example, it is 3,000 to 30,000. Monomer (a42) is preferably a macromonomer whose main component is at least one selected from alkyl (meth)acrylates, styrene monomers, and (meth)acrylonitrile, and more preferably a macromonomer selected from C(meth)acrylate. 1-4 A macromonomer whose main component is at least one of alkyl esters, styrene, and (meth)acrylonitrile. It should be noted that the main component refers to a component constituting the macromonomer that is, for example, 50% or more by mass, preferably 80% or more by mass, and more preferably 90% or more by mass. As monomer (a42), commercially available products such as AA-6, AS-6, AN-6S, AB-6, AW-6S, AK-5, and AK-32 manufactured by Toa Synthetic Co., Ltd. may also be used.
[0077] The content of structural unit (A42) derived from the monomer (a42) is, for example, 0 to 50% by mass in 100% by mass of copolymer (A), preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.
[0078] The weight-average molecular weight of copolymer (A) is, for example, 500,000 to 6,000,000, preferably 1,000,000 to 4,000,000, more preferably 1,200,000 to 3,500,000, but may also be 1,800,000 to 3,500,000, 2,000,000 to 3,500,000 or 2,500,000 to 3,500,000.
[0079] The refractive index of the copolymer (A) is, for example, 1.50 to 1.65, preferably 1.52 to 1.63, and more preferably 1.55 to 1.60.
[0080] The copolymer (A) can be manufactured by copolymerizing (meth)acrylate monomers (a). The polymerization method is not particularly limited, but bulk polymerization using thermal or photopolymerization initiators is preferred.
[0081] Examples of thermal polymerization initiators include: 2,2'-azobisisobutyronitrile (AIBN), 2,2'-azobis(2-methylbutyronitrile), azodicyanovalerate, 2,2'-azobis(4-methoxy-2,4-dimethylvaleritrile), 2,2'-azobis(2,4-dimethylvaleritrile), dimethyl 2,2'-azobis(2-methylpropionate), 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carboxylonitrile), 2,2'-azobis[N-(2-propenyl)-2-methylpropionamide], 2,2'-azobis(N-butyl-2-methylpropionamide), 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride, 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride, and 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride. Azo compounds including 2,2'-azobis(2-methylpropane)dihydrate, 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropane]hydrate, 2,2'-azobis[2-(2-imidazoline-2-yl)propane], 2,2'-azobis(1-imino-1-pyrrolidine-2-methylpropane)dihydrochloride, 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propamide], etc.; organic peroxides including tert-butyl peroxypentanoate, tert-butyl peroxybenzoate, tert-butyl peroxy-2-ethylhexanoate, di-tert-butyl peroxide, cumene hydroperoxide, benzoyl peroxide, tert-butyl hydroperoxide, etc.; and inorganic peroxides including hydrogen peroxide, ammonium persulfate, potassium persulfate, sodium persulfate, etc. These thermal polymerization initiators can be used alone or in combination of two or more.
[0082] Examples of photopolymerization initiators include: acetophenone, 3-methylacetophenone, benzoyladium dimethyl ketal, 2,2-dimethoxy-1,2-diphenylethane-1-one, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropane-1-one, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinylpropane-1-one, 2-hydroxy-2-methyl-1-phenylpropane-1-one, 1-hydroxycyclohexylphenyl ketone, and other phenylalkyl ketones; benzophenones, primarily benzophenone, 4-chlorobenzophenone, and 4,4'-diaminobenzophenone; benzoin ethers, such as benzoin propyl ether and benzoin ethyl ether; thioxanthones, such as 4-isopropylthioxanthone; xanthone; fluorenone; camphorquinone; benzaldehyde; anthraquinones, etc. These photopolymerization initiators can be used alone or in combination of two or more.
[0083] Chain transfer agents can also be used in copolymerization reactions. Examples of chain transfer agents include thiols such as methyl mercaptan, tert-butyl mercaptan, decyl mercaptan, benzyl mercaptan, stearyl mercaptan, n-dodecyl mercaptan, tert-dodecyl mercaptan, mercaptoacetic acid, mercaptopropionic acid and its esters (such as 2-ethylhexyl 3-mercaptopropionic acid), 2-ethylhexyl mercaptoethanol, and octyl mercaptoacetate; alcohols such as methanol, ethanol, propanol, n-butanol, isopropanol, tert-butanol, hexanol, benzyl alcohol, and allyl alcohol; halogenated hydrocarbons such as chloroethane, fluoroethane, and trichloroethylene; carbonyl groups such as acetone, methyl ethyl ketone, cyclohexanone, acetophenone, acetaldehyde, propionaldehyde, n-butyraldehyde, furfural, and benzaldehyde; methyl-4-cyclohexene-1,2-dicarboxylic anhydride; and α-methylstyrene. These chain transfer agents can be used alone or in combination of two or more.
[0084] Bulk polymerization using photoinitiators (hereinafter referred to as photopolymerization) can include, for example, the addition of raw monomers and photoinitiators, followed by irradiation with active energy rays under a nitrogen atmosphere at a reaction start temperature of 20°C or higher and 35°C or lower. If the temperature within the reaction system rises by 5°C or higher but less than 20°C from the reaction start temperature, air or the like is introduced into the reaction system to stop the reaction, a copolymer (A) can be obtained.
[0085] Examples of active energy rays used in photopolymerization include ultraviolet light, lasers, alpha rays, beta rays, gamma rays, X-rays, and electron beams. From the perspectives of controllability, operability, and cost, ultraviolet light is preferred. Ultraviolet light with wavelengths between 200 nm and 400 nm is even more preferred. Ultraviolet light can be emitted using light sources such as high-pressure mercury lamps, microwave-excited lamps, chemical lamps, black lights, LEDs (Light-Emitting Diodes), and metal halide lamps.
[0086] In bulk polymerization using a thermal polymerization initiator (hereinafter referred to as thermal bulk polymerization), the temperature and time of the copolymerization reaction can be appropriately combined, for example, within the range of reaction temperature 40°C to 90°C and reaction time 0.1 to 10 hours or 1 to 10 hours. Preferred reaction conditions are those that leave a required amount of residual monomer (a) and produce copolymer (A), for example, a combination of reaction temperature below 70°C and reaction time below 2 hours selected from the above range.
[0087] It should be noted that, depending on the polymerization conditions, the copolymerization reaction may sometimes proceed until the amount of residual monomer (a) after polymerization is insufficient. In such cases, if monomer (a) is added after the reaction is complete, the adhesive composition of the present invention can be prepared.
[0088] 1.2 (Meth)acrylate monomers (a) As described above, the adhesive composition contains a (meth)acrylate monomer (a). By containing the (meth)acrylate monomer (a), the dispersibility of the inorganic particles (B) can be improved, and the transparency of the adhesive layer can be improved. The (meth)acrylate monomer (a) can be an unreacted monomer (a) that remains unchanged after polymerization of the (meth)acrylate copolymer (A) (so-called residual monomer), or a monomer (a) added after the reaction, or a mixture thereof.
[0089] When the monomer (a) in the adhesive composition consists only of the residual monomer, the monomer (a1) that becomes the structural unit (A1) is identical to the monomer (a1) in the adhesive composition. Similarly, the monomer (a2) that becomes the structural unit (A2) is identical to the monomer (a2) in the adhesive composition, and the monomer (a3) that becomes the structural unit (A3) is identical to the monomer (a3) in the adhesive composition.
[0090] The content of monomer (a) is, for example, 45 to 95% by mass, preferably 55 to 93% by mass, more preferably 63 to 90% by mass, further preferably 70 to 90% by mass, and particularly preferably 75 to 90% by mass, out of a total of 100% by mass of copolymer (A) and said monomer (a). By making the amount of monomer (a) appropriate, the adhesive layer can exhibit excellent transparency even when the thickness of the adhesive layer is increased.
[0091] As monomers (a), they include aromatic monomers (a1), hydroxyl-containing monomers (a2), etc., and other monomers (a3) may be included as needed. Specific examples and preferred examples of these are the same as those described for the copolymer (A) above. The content of each monomer in the total 100% by mass of monomers (a) in the adhesive composition is as follows, for example.
[0092] The content of aromatic monomers (a1) is, for example, 40 to 99% by mass, preferably 50 to 95% by mass, and more preferably 70 to 90% by mass.
[0093] The content of the hydroxyl-containing monomer (a2) is, for example, 1 to 40% by mass, preferably 3 to 30% by mass, more preferably 7 to 25% by mass. It may also be 12 to 25% by mass.
[0094] The content of other monomers (a3) is, for example, 0 to 50% by mass, preferably 1 to 50% by mass, more preferably 1 to 40% by mass, even more preferably 5 to 25% by mass, and particularly preferably 5 to 20% by mass.
[0095] The content of (meth)acrylate monomers (a31) containing alicyclic hydrocarbon groups is, for example, 0 to 50% by mass, preferably 5 to 40% by mass, more preferably 10 to 30% by mass, and even more preferably 10 to 20% by mass.
[0096] The content of nitrogen-containing (meth)acrylate monomer (a32) is, for example, 0 to 50% by mass, preferably 1 to 30% by mass, more preferably 5 to 20% by mass, and even more preferably 5 to 10% by mass.
[0097] The content of alkoxyalkyl (meth)acrylate monomer (a33) is, for example, 0 to 50% by mass, preferably 5 to 40% by mass, and more preferably 10 to 30% by mass.
[0098] The content of the low Tg (meth)acrylate alkyl monomer (a34) with a glass transition temperature of -20°C or below in the homopolymer is, for example, 0 to 50% by mass, preferably 0 to 30% by mass, and more preferably 1 to 20% by mass.
[0099] The content of (meth)acrylate alkyl ester monomers (a35) with a glass transition temperature exceeding -20°C is, for example, 0 to 50% by mass, preferably 0 to 10% by mass, and more preferably 0 to 5% by mass.
[0100] The content of the acid-containing monomer (a36) is, for example, 0 to 50% by mass, preferably 0 to 30% by mass, more preferably 0 to 10% by mass, or 0% by mass.
[0101] The content of (meth)acrylate monomers (a37) having acyl or epoxy groups is, for example, 0 to 50% by mass, preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.
[0102] The content of (meth)acrylic monomer (a38) with phosphate group is, for example, 0 to 50% by mass, preferably 0 to 20% by mass, more preferably 0 to 10% by mass.
[0103] The content of the sulfonic acid group-containing monomer (a39) is, for example, 0 to 50% by mass, preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.
[0104] The content of the silane-containing vinyl monomer (a40) is, for example, 0 to 50% by mass, preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.
[0105] The content of styrene monomer (a41) is, for example, 0 to 50% by mass, preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.
[0106] The content of macromonomer (a42) is, for example, 0 to 50% by mass, preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.
[0107] The total content of aromatic monomer (a1) and hydroxyl-containing monomer (a2) in the adhesive composition is, for example, 50-100% by mass of monomer (a), preferably 60-99% by mass, more preferably 75-95% by mass, or possibly 85-100% by mass or 95-100% by mass. Furthermore, the mass ratio (a1 / a2) of aromatic monomer (a1) to hydroxyl-containing monomer (a2) is, for example, 50 / 50-99 / 1, preferably 70 / 30-98 / 2, more preferably 75 / 25-95 / 5, even more preferably 80 / 20-90 / 10, and particularly preferably 83 / 17-89 / 11.
[0108] It should be noted that the proportions of monomers (a1), (a2), and (a3) (specifically (a31) to (a42)) in monomer (a) of the adhesive composition can be determined by separating monomer (a) from copolymer (A) using solid-liquid separation, extraction, etc., and then analyzing the separated material using gas chromatography, NMR, etc. Furthermore, if monomer (a) is a residual monomer, and the proportions of monomers (a1), (a2), and (a3) (specifically (a31) to (a42)) at the time of polymerization are known to be equal to the proportions of the residual monomers, the proportions of monomers (a1), (a2), and (a3) (specifically (a31) to (a42)) in the adhesive composition can be determined based on the charge ratio instead of analysis.
[0109] 1.3 Inorganic particles (B) The adhesive composition contains inorganic particles (B). By including inorganic particles (B), the refractive index of the adhesive layer can be increased, making it suitable for use as an adhesive for optical films.
[0110] Examples of inorganic particles (B) include aluminum oxide, titanium oxide, zirconium oxide (zirconia), indium oxide, zinc oxide, tin oxide, lanthanum oxide, yttrium oxide, cerium oxide, magnesium oxide, niobium oxide, tantalum oxide, indium tin oxide, antimony tin oxide, barium titanate, strontium titanate, perovskite, spinel, etc., with aluminum oxide, titanium oxide, zirconium oxide, and zinc oxide being preferred, and zirconium oxide being more preferred. One of these can be used, or a combination of two or more can be used.
[0111] The inorganic particles (B) are preferably coated with a coating agent such as a carboxylic acid compound. Examples of carboxylic acid compounds include: Straight-chain saturated aliphatic carboxylic acids such as oxalic acid, malonic acid, butyric acid, succinic acid, valeric acid, glutaric acid, hexanoic acid, adipic acid, heptanoic acid, octanoic acid, nonanoic acid, decanoic acid, dodecanoic acid, tetradecanoic acid, palmitic acid, and stearic acid. Branched saturated aliphatic carboxylic acids such as neopentanoic acid, 2,2-dimethylbutyric acid, 3,3-dimethylbutyric acid, 2,2-diethylbutyric acid, 3,3-diethylbutyric acid, 2-ethylhexanoic acid, 2-methylheptanoic acid, 4-methyloctanoic acid, and neodecanoic acid. Carboxylic acids containing alicyclic hydrocarbon groups, such as cycloalkanoic acids and cyclohexanedicarboxylic acid; Acrylic acid, methacrylic acid, maleic acid, fumaric acid, oleic acid, linoleic acid, linolenic acid and other straight-chain unsaturated aliphatic carboxylic acids; Carboxylic acids containing ether bonds, such as methoxyacetic acid, ethoxyacetic acid, 3-ethoxypropionic acid, 2-methoxyethoxyacetic acid, and 2-methoxyethoxyethoxyacetic acid; Lactic acid, malic acid, citric acid, hydroxystearic acid, and other carboxylic acids containing hydroxyl groups; Pyruvic acid and other carboxylic acids containing carbonyl groups; Aromatic carboxylic acids such as benzoic acid, phthalic acid, and isophthalic acid; Carboxylic acids containing (meth)acryloyl groups, such as 2-acryloyloxyethyl succinic acid, 2-methacryloyloxyethyl succinic acid, 2-acryloyloxyethyl hexahydrophthalic acid, 2-methacryloyloxyethyl hexahydrophthalic acid, 2-acryloyloxyethyl phthalic acid, and 2-methacryloyloxyethyl phthalic acid.
[0112] The inorganic particles (B) are preferably coated with carboxylic acid compounds (especially monocarboxylic acid compounds) having a total carbon number of 6 or more (preferably 7 or more), and more preferably with branched saturated aliphatic carboxylic acids (especially monocarboxylic acid compounds) having a total carbon number of 6 or more (preferably 7 or more). Furthermore, the inorganic particles (B) are preferably coated with two or more carboxylic acid compounds, at least preferably with branched saturated aliphatic carboxylic acids having a total carbon number of 6 or more (preferably 7 or more), and also with carboxylic acids containing ether bonds.
[0113] As a branched saturated aliphatic carboxylic acid, a branched saturated aliphatic carboxylic acid with a total carbon number of 9 or less is preferred, a branched saturated aliphatic carboxylic acid with a total carbon number of 8 or less is more preferred, and 2-ethylhexanoic acid is particularly preferred.
[0114] As a carboxylic acid containing an ether bond, methoxyacetic acid, ethoxyacetic acid, 3-ethoxypropionic acid, 2-methoxyethoxyacetic acid, and 2-methoxyethoxyethoxyacetic acid are preferred, methoxyacetic acid and ethoxyacetic acid are more preferred, and methoxyacetic acid is even more preferred.
[0115] The refractive index of the inorganic particles (B) is, for example, 1.60 to 2.72 (titanium dioxide rutile type), preferably 1.65 to 2.50, and more preferably 1.70 to 2.20.
[0116] The volume average particle size of the inorganic particles (B) is, for example, 1–100 nm, preferably 3–30 nm, and more preferably 5–20 nm. The smaller the volume average particle size, the more difficult it is to disperse the inorganic particles (B), but on the other hand, the higher the transparency when dispersion is successful. It should be noted that the volume average particle size of the inorganic particles (B) can be determined based on dynamic light scattering.
[0117] Furthermore, the number-average particle size of the inorganic particles (B) is, for example, 1–100 nm, preferably 3–30 nm, and even more preferably 5–20 nm. It should be noted that the number-average particle size of the inorganic particles (B) can be determined by measuring the length of the long axis of any 100 inorganic particles (B) using an electron microscope and calculating their average value.
[0118] In the particle size determination of inorganic particles (B) using dynamic light scattering, the ratio of the cumulative 90% particle size D90 of the volume reference to the cumulative 50% particle size D50 of the volume reference (D90 / D50) is, for example, 3.0 or less, preferably 2.5 or less, and more preferably 2.0 or less. The smaller the D90 / D50 ratio, the easier it is for the inorganic particles (B) to disperse uniformly.
[0119] When the inorganic particles (B) are zirconium oxide, the half-width at half-maximum (WHM) of the (101) plane in XRD (X-ray diffraction) measurements using CuKα rays as the light source is preferably 1.20° or less. By setting the WHM to 1.20° or less, the crystallite size increases, which improves the refractive index. The WHM is preferably 0.6° to 1.1°, more preferably 0.65° to 1.0°, and even more preferably 0.7° to 1.0°. By setting the WHM to 0.6° or more, the transparency of the adhesive layer can be further improved.
[0120] When the inorganic particles (B) are coated zirconium oxide, the refractive index of the zirconium oxide particles is preferably 1.7 or higher, more preferably 1.8 to 2.2, and even more preferably 1.8 to 1.9.
[0121] The amount of inorganic particles (B) in the adhesive composition is, for example, 20 to 2000 parts by mass relative to a total of 100 parts by mass of copolymer (A) and monomer (a), preferably 50 to 1500 parts by mass, more preferably 80 to 1000 parts by mass, and may also be 80 to 600 parts by mass or 80 to 350 parts by mass. By adjusting the proportion of inorganic particles (B) within the above range, it is easier to balance refractive index and transparency.
[0122] The total content of the copolymer (A), monomer (a), and inorganic particles (B) in the adhesive composition is preferably 80-100% by mass of 100% by weight of the solids component of the adhesive composition, more preferably 90-99.9% by mass, and even more preferably 95-99.9% by mass. It should be noted that, in this specification, the solids component refers to the component after solvent removal.
[0123] 1.4 Silane Coupling Agent (C) The adhesive composition preferably further comprises a silane coupling agent (C). The inclusion of a silane coupling agent (C) improves the durability of the adhesive layer and enhances the adhesion between the adhesive layer and the substrate (especially glass).
[0124] Examples of silane coupling agents (C) include silane coupling agents (especially di- or trialkoxysilanes) having reactive groups such as epoxy (glycidoxy), polymerizable groups (vinyl, (meth)acryloyl, etc.), amino, mercapto, halogen atoms, and isocyanate groups, as well as silane coupling agents (especially di- or trialkoxysilanes) having hydrocarbon groups. Silane coupling agents with reactive groups are preferred, and silane coupling agents with epoxy (glycidoxy) groups are more preferred.
[0125] Examples of epoxy-containing silane coupling agents (C1) include 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, γ-glycidoxypropyltrimethoxysilane, and γ-glycidoxypropyltriethoxysilane.
[0126] Examples of silane coupling agents (C2) with polymerizable groups include vinyltrichlorosilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(β-methoxyethoxy)silane, γ-methacryloxypropylmethyldimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldiethoxysilane, γ-methacryloxypropyltriethoxysilane, and γ-acryloxypropyltrimethoxysilane.
[0127] Examples of amino-containing silane coupling agents (C3) include N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, and N-phenyl-γ-aminopropyltrimethoxysilane.
[0128] Examples of silane coupling agents (C4) with thiol groups include γ-mercaptopropyltrimethoxysilane, γ-mercaptopropylmethyldimethoxysilane, and bis-(3-[triethoxysilyl]propyl)tetrasulfide.
[0129] Examples of silane coupling agents (C5) having halogen atoms (especially halogenated hydrocarbon groups) include γ-chloropropyltrimethoxysilane.
[0130] Examples of silane coupling agents (C6) with hydrocarbon groups include methyltrimethoxysilane, dimethyldimethoxysilane, trimethylmethoxysilane, n-propyltrimethoxysilane, ethyltrimethoxysilane, diethyldiethoxysilane, n-butyltrimethoxysilane, n-hexyltriethoxysilane, n-octyltrimethoxysilane, phenyltrimethoxysilane, diphenyldimethoxysilane, and cyclohexylmethyldimethoxysilane.
[0131] The silane coupling agent (C) may also be a combination of two silane coupling agents or their reactants, in which the reactive groups react with each other. Alternatively, a compound with a hydrolyzable silane group may be obtained by reacting other coupling agents, polyisocyanates, etc., onto the reactive groups of a silane coupling agent having reactive groups.
[0132] The silane coupling agent (C) can be obtained from Shin-Etsu Chemical Industry Co., Ltd., for example as KBM-303, KBM-403, KBE-402, KBE-403, KBE-502, KBE-503, KBM-5103, KBM-573, KBM-802, KBM-803, KBE-846, KBE-9007, etc.
[0133] The silane coupling agent (C) can be used alone or in combination of two or more.
[0134] The amount of silane coupling agent (C) in the adhesive composition is, for example, 0.001 to 5 parts by mass, preferably 0.001 to 4 parts by mass, and more preferably 0.01 to 3 parts by mass, relative to a total of 100 parts by mass of copolymer (A) and monomer (a). The more silane coupling agent (C) present, the better the durability of the adhesive layer. Furthermore, by avoiding an excess of silane coupling agent (C), thermal foaming caused by low molecular weight compounds can be suppressed.
[0135] 1.5 Crosslinking agent (D) The adhesive composition preferably further comprises a crosslinking agent (D). The crosslinking agent (D) can react with the copolymer (A) to form a crosslinked structure, which can improve the adhesion (bonding) of the adhesive layer and improve its durability.
[0136] Examples of crosslinking agents (D) include isocyanate compounds (D1), carbodiimide compounds (D2), oxazoline compounds (D3), epoxy compounds (D4), polyfunctional (meth)acrylate monomers (D5), polyfunctional allyl monomers (D6), and peroxides (D7). One or more of these can be used, or a combination of two or more can be employed. When combining two or more, two or more crosslinking agents of the same type can be combined (e.g., two or more polyfunctional (meth)acrylate monomers (D5)), or one or more crosslinking agents of different types can be combined (e.g., one isocyanate compound (D1) and one peroxide (D7)).
[0137] Examples of isocyanate compounds (D1) include: dimer diisocyanates, 2,4-toluene diisocyanate (2,4-TDI), 2,6-toluene diisocyanate (2,6-TDI), 4,4'-diphenylmethane diisocyanate (4,4'-MDI), 2,4'-diphenylmethane diisocyanate (2,4'-MDI), 1,4-phenylene diisocyanate, phenylenediamine diisocyanate (XDI), tetramethylphenylenediamine diisocyanate (TMXDI), benzyl toluidine diisocyanate (TODI), and 1,5-naphthalene diisocyanate (NDI). Aromatic diisocyanates such as , , etc.; aliphatic diisocyanates such as allyl isocyanate, hexamethylene diisocyanate (HDI), trimethylhexamethylene diisocyanate (TMHDI), lysine diisocyanate, norbornane diisocyanate methyl (NBDI); alicyclic diisocyanates such as transcyclohexane-1,4-diisocyanate, isophorone diisocyanate (IPDI), H6-XDI (hydrogenated XDI), H12-MDI (hydrogenated MDI); carbodiimide-modified diisocyanates of the above diisocyanates; or isocyanurate-modified diisocyanates of these diisocyanates, etc. Additions of the above isocyanate compounds (D1) with polyols such as trimethylolpropane, polytetramethylene ether glycol (PTMG), and polypropylene glycol (PPG), biuret forms or isocyanurate forms of these isocyanate compounds (D1) may also be used appropriately.
[0138] Isocyanate compounds (D1) are available from Tosoh Corporation as Coronate (registered trademark, hereinafter the same) L, Coronate HL, Coronate HX, Coronate 2030, Coronate 2031, etc.; from Mitsui Chemicals Corporation as Takenate (registered trademark, hereinafter the same) D-102, Takenate D-110N, Takenate D-200, Takenate D-202, etc.; and from Mitsui Chemicals Corporation as Durnate (registered trademark, hereinafter the same) 24A-100, Durnate TPA-100, Durnate TKA-100, Durnate P301-75E, Durnate E402-90T, Durnate E405-80T, Durnate TSE-100, Durnate D-101, Durnate, etc. D-201, etc., were obtained from Asahi Kasei Corporation; Sumidur (registered trademark) N-75, N-3200, N-3300, etc., were obtained from Sumika Covestro Urethane Co., Ltd.; Sanprene (registered trademark, hereinafter the same) P-6090 (PTMG / MDI series), Sanprene P-663L (PTMG / TDI series), Sanprene P-664 (PTMG / TDI series), Sanprene P-665 (PTMG / TDI series), Sanprene P-667 (PTMG / TDI series), Sanprene P-868 (PTMG / HMDI series), Sanprene P-870 (PTMG / HMDI series), Sanprene C-810 (PPG / TDI series), etc., were obtained from Sanyo Chemical Industries, Ltd.
[0139] The isocyanate compound (D1) is preferably used in its uncapped form, but it can also be a capped isocyanate compound obtained by reacting with a capping agent that protects the isocyanate group. Examples of capped isocyanate compounds include: Duranate MF-B60X (capped 1,6-hexamethylene diisocyanate) and Duranate MF-K60X (capped 1,6-hexamethylene diisocyanate) manufactured by Asahi Kasei Corporation; Coronate AP-M, 2503, 2507, 2513, 2515, and Millionate (registered trademark) MS-50 manufactured by Tosoh Corporation; and Takenate manufactured by Mitsui Chemicals Co., Ltd. B-830 (terminated toluene diisocyanate), B-815N (terminated 4,4'-methylene bis(cyclohexyl isocyanate)), B-842N (terminated 1,3-bis(isocyanatomethyl)cyclohexane), B-846N (terminated 1,3-bis(isocyanatomethyl)cyclohexane), B-874N (terminated isophorone diisocyanate), B-882N (terminated 1,6-hexamethylene diisocyanate), etc.; DIC Corporation The products include Burnock (registered trademark) D-500 (terminated toluene diisocyanate) and D-550 (terminated 1,6-hexamethylene diisocyanate), manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd.; and Elastron (registered trademark) BN-P17 (terminated 4,4'-diphenylmethane diisocyanate), BN-04, BN-08, BN-44, and BN-45 (all termed end-terminated urethane-modified polyisocyanates), manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd. Among these, Duranat MF-K60X is preferred.
[0140] As a carbodiimide compound (D2), for example, a high molecular weight polycarbodiimide can be generated by decarboxylation condensation of diisocyanate (D22) in the presence of a carbodiimide catalyst (D21). Examples of diisocyanates (D22) supplied for the decarboxylation condensation reaction include: 4,4'-diphenylmethane diisocyanate, 3,3'-dimethoxy-4,4'-diphenylmethane diisocyanate, 3,3'-dimethyl-4,4'-diphenylmethane diisocyanate, 4,4'-diphenyl ether diisocyanate, 3,3'-dimethyl-4,4'-diphenyl ether diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 1-methoxyphenyl-2,4-diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, tetramethylphenyldimethyl diisocyanate, etc.
[0141] Examples of carbodiimide catalysts (D21) used in the decarboxylation condensation reaction include: 1-phenyl-2-phosphacyclopentene-1-oxide, 3-methyl-2-phosphacyclopentene-1-oxide, 1-ethyl-3-methyl-2-phosphacyclopentene-1-oxide, 1-ethyl-2-phosphacyclopentene-1-oxide, or their 3-phosphacyclopentene isomers, etc.
[0142] As an oxazoline compound (D3), a polymer containing an oxazoline group is preferred. Examples include: an oxazoline-containing acrylic / styrene polymer whose main chain comprises an acrylic backbone and a styrene backbone and whose side chains of the main chain have oxazoline groups; and an oxazoline-containing acrylic polymer whose main chain comprises an acrylic backbone and whose side chains of the main chain have oxazoline groups.
[0143] Examples of oxazoline groups include 2-oxazoline, 3-oxazoline, and 4-oxazoline, with 2-oxazoline being preferred. Furthermore, the polymer containing the oxazoline group may also contain polyoxyalkylene groups in addition to the oxazoline group.
[0144] Examples of oxazoline compounds (D3) include: Epocros (registered trademark) WS-300, Epocros (registered trademark) WS-500, and Epocros (registered trademark) WS-700 manufactured by Nippon Shokubai Co., Ltd.; and Epocros (registered trademark) K-1000 series and Epocros (registered trademark) K-2000 series manufactured by Nippon Shokubai Co., Ltd., which are acrylic / styrene polymers containing oxazoline groups.
[0145] As the epoxy compound (D4), known epoxy crosslinking agents can be used, such as: "TETRAD-C" and "TETRAD-X" manufactured by Mitsubishi Gas Chemical Co., Ltd.; "Adeka Resin EPU series" and "Adeka Resin EPR series" manufactured by ADEKA Co., Ltd.; and liquid epoxy resins such as "Celloxide" manufactured by Daicel Co., Ltd. These liquid epoxy resins are preferred in that they facilitate the mixing process when manufacturing adhesive compositions.
[0146] The polyfunctional (meth)acrylate monomer (D5) is a (meth)acrylate monomer having multiple (two or more) (meth)acryloyl groups. Hereinafter, a (meth)acrylate monomer having N (meth)acryloyl groups in one molecule is sometimes referred to as an N-functional monomer. Examples of such (meth)acrylate monomers include hydrocarbon-based polyfunctional monomers (D51) or hydrocarbon ether-based polyfunctional monomers (D52). The hydrocarbon-based or hydrocarbon ether-based polyfunctional monomers (D51) (D52) are preferably compounds obtained by esterifying the hydroxyl groups of a polyol with a hydrocarbon or hydrocarbon ether group as the main skeleton having 10 or more and 100 or fewer carbon atoms by (meth)acrylate. From the viewpoint of improving adhesion (adhesion) through crosslinking, such compounds are preferred. Examples of hydrocarbon groups in the polyol include straight-chain or branched aliphatic hydrocarbon groups, aromatic hydrocarbon groups, alicyclic hydrocarbon groups, and hydrocarbon groups formed by combinations of these hydrocarbon groups. Examples of hydrocarbon ether groups include those obtained by etherification of the hydrocarbon group. Furthermore, examples of polyols with a hydrocarbon ether group as the main backbone include compounds obtained by adding an epoxide with 2 or more but less than 4 carbon atoms to the polyol (addition number 1 or more but less than 30). Also, examples of polyalkylene glycols (addition number 1 or more but less than 30) obtained from epoxides with 2 or more but less than 4 carbon atoms can be included.
[0147] Examples of difunctional monomers (D511) among the polyfunctional monomers (D51) of the aforementioned hydrocarbon system include: di(meth)acrylates of alkylene glycols such as ethylene glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and neopentyl glycol di(meth)acrylate; di(meth)acrylates of diols containing alicyclic hydrocarbon groups such as cyclohexanediethanol di(meth)acrylate and tricyclodecanediethanol di(meth)acrylate (dihydroxymethyl-tricyclodecanediacrylate); and di(meth)acrylates of diols containing aromatic hydrocarbon groups such as bisphenol A di(meth)acrylate.
[0148] Examples of difunctional monomers (D521) among the polyfunctional monomers (D52) of the hydrocarbon ether system include: alkoxylated hexanediol di(meth)acrylate, alkoxylated cyclohexanediethanol di(meth)acrylate, alkoxylated di(meth)acrylate, alkoxylated neopentyl glycol di(meth)acrylate, alkoxylated bisphenol A di(meth)acrylate, etc., which are di(meth)acrylates of compounds obtained by adding alkylene glycols or diols described in the above-mentioned hydrocarbon difunctional monomers (D511). Furthermore, more specific examples of difunctional monomers (D521) in the hydrocarbon ether system include: di(meth)acrylates of polyalkylene glycols such as diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, and dipropylene glycol di(meth)acrylate; and dioxanediol di(meth)acrylate, etc.
[0149] Examples of trifunctional to hexafunctional monomers among the hydrocarbon or hydrocarbon ether polyfunctional monomers (D51) (D52) include, for example, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, glycerol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, trimethylolpropane tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, etc., which are tri(meth)acrylates, tetra(meth)acrylates, penta(meth)acrylates, or hexa(meth)acrylates of tri(meth)acrylates, tetra(meth)acrylates, penta(meth)acrylates, or hexa(meth)acrylates of compounds obtained by adding epoxides to these tri(meth)acrylates, tetra(meth)acrylates, penta(meth)acrylates, or hexa(meth)acrylates.
[0150] The polyfunctional (meth)acrylate monomer (D5) can be any (meth)acrylate monomer having multiple (two or more) (meth)acryloyl groups, and can also be a monomer other than the aforementioned hydrocarbon or hydrocarbon ether polyfunctional monomers (D51) (D52). Examples of such monomers include polyester poly(meth)acrylates and epoxy (meth)acrylates having two or more (meth)acryloyl groups at the end.
[0151] Among these polyfunctional (meth)acrylate monomers (D5), polyfunctional monomers (D51) and / or polyfunctional monomers (D52) are preferred, and polyfunctional monomers (D51) and / or polyfunctional monomers (D52) that are trifunctional to hexafunctional monomers are more preferred.
[0152] A polyfunctional allyl monomer (D6) is a monomer having at least one allyl group and containing multiple (two or more) radical polymerizable functional groups. Examples of such monomers include allyl methacrylate, diallyl phthalate (DAP), trimethylolpropane diallyl ether, pentaerythritol triallyl ether, and triallyl isocyanurate.
[0153] From the viewpoint of productivity and stability, the peroxide (D7) preferably has a 1-minute half-life temperature of 80–160°C, more preferably 80–140°C, even more preferably 80–125°C, and particularly preferably 90–125°C. "The half-life of the peroxide" refers to the time until the residual amount of the peroxide is reduced to half, and can be referenced from the manufacturer's product catalog values, such as those listed in the ninth edition of the Organic Peroxides Catalog published by Nippon Oil Co., Ltd. (May 2003).
[0154] Examples of peroxides (D7) include: diisopropyl peroxide (1-minute half-life temperature 88.3°C; hereinafter, temperatures in parentheses indicate 1-minute half-life temperatures), di(2-ethylhexyl) peroxide (90.6°C), bis(4-tert-butylcyclohexyl) peroxide (92.1°C), disec-butyl peroxide (92.4°C), tert-butyl peroxyneodecanate (103.5°C), tert-hexyl peroxynepentanoate (109.1°C), and tert-butyl peroxynepentanoate (1...). Examples of peroxides include: 10.3℃, dilauroyl peroxide (116.4℃), bis(n-octanoyl) peroxide (117.4℃), 1,1,3,3-tetramethylbutyl peroxide-2-ethylhexanoate (124.3℃), di(4-methylbenzoyl) peroxide (128.2℃), benzoyl peroxide (130.0℃), a mixture of benzoyl peroxide, benzoyl-m-methylbenzoyl peroxide, and m-toluyl peroxide (131.1℃), and tert-butyl peroxide butyrate (136.1℃). Among these, diisopropyl peroxide, bis(4-tert-butylcyclohexyl) peroxide, and tert-butyl peroxyneodecanate are preferred. These can be used individually or in combination of two or more. As a combination of two or more, a combination of bis(4-tert-butylcyclohexyl) peroxide and dilauroyl peroxide is preferred.
[0155] Peroxide (D7) can be used as trade names such as: "Pereroyl (registered trademark, hereinafter the same) IB" (85.1℃), "Percumyl (registered trademark, hereinafter the same) ND" (94.0℃), "Pereroyl NPP" (94.0℃), "Pereroyl IPP" (88.3℃), "Pereroyl SBP" (92.4℃), "Perocta (registered trademark, hereinafter the same) ND" (92.4℃), "PereroylTCP" (92.1℃), "Pereroyl OPP" (90.6℃), "Perhexyl (registered trademark, hereinafter the same) ND" (100.9℃), "Perbutyl (registered trademark, hereinafter the same) ND" (103.5℃), "Perbutyl NHP" (104.6℃), "PerhexylPV" (109.1℃), "Perbutyl PV" (110.3℃), "Pereroyl 355" (112.6℃), "Pereroyl L" (116.4℃), "Perocta ... Perhexa O (124.3℃), Peroyl SA (131.8℃), Perhexa 25O (118.8℃), Perhexyl O (132.6℃), NYPER PMB (128.2℃), Perbutyl O (134.0℃), NYPER BMT (131.1℃), NYPER BW (130.0℃), NYPER BMT-K40 (131.1℃), NYPER BMT-M (131.1℃), Perhexa MC (142.1℃), Perhexa TMH (147.1℃), Perhexa HC (149.2℃), Perhexa C (153.8℃), Pertetra A (153.8℃), Perhexyl I (155.0℃), Perbutyl The grades “L” (159.4℃), “Perbutyl I” (158.8℃), “Perhexa 25Z” (158.2℃), “Perbutyl A” (159.9℃), and “Perhexa 22” (159.9℃) were obtained from Nippon Oil Co., Ltd.
[0156] Relative to a total of 100 parts by weight of copolymer (A) and monomer (a), the amount of crosslinking agent (D) in the adhesive composition is preferably 0.001 to 5 parts by weight, more preferably 0.005 to 3 parts by weight, even more preferably 0.01 to 1 part by weight, and particularly preferably 0.02 to 0.2 parts by weight. When the content of crosslinking agent (D) is within the said range, durability can be further improved.
[0157] 1.6 Photopolymerization Initiator (E) The adhesive composition of the present invention is preferably a photocurable adhesive composition. Specifically, the adhesive composition preferably contains a photopolymerization initiator (E). By containing a photopolymerization initiator (E), the monomer (a) can be cured after application. As a photopolymerization initiator, photopolymerization initiators listed above that can be used in the polymerization of copolymers (A) can be used.
[0158] The amount of photopolymerization initiator (E) in the adhesive composition is, for example, 0.001 to 10 parts by mass relative to a total of 100 parts by mass of copolymer (A) and monomer (a), preferably 0.01 to 5 parts by mass, and more preferably 0.05 to 1 part by mass.
[0159] 1.7 Chain transfer agent (F) The adhesive composition may also contain a chain transfer agent (F). By including a chain transfer agent (F), the molecular weight can be controlled when the monomer (a) is cured after application. As the chain transfer agent (F), chain transfer agents listed that can be used in the polymerization of the copolymer (A) can be used.
[0160] The amount of chain transfer agent (F) in the adhesive composition is, for example, 0.001 to 10 parts by mass relative to a total of 100 parts by mass of copolymer (A) and monomer (a), preferably 0.01 to 5 parts by mass, and more preferably 0.05 to 1 part by mass.
[0161] 1.8 Solvent (G) The adhesive composition may also contain a solvent (G). By including a solvent (G), the viscosity of the adhesive composition can be adjusted. Examples of solvents (G) include esters such as ethyl acetate and n-butyl acetate; aromatic hydrocarbons such as toluene and benzene; aliphatic hydrocarbons such as n-hexane and n-heptane; alicyclic hydrocarbons such as cyclohexane and methylcyclohexane; ketones such as methyl ethyl ketone, methyl isobutyl ketone, and acetone; and glycol ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, propylene glycol monomethyl ether, diethylene glycol monomethyl ether, and ethylene glycol dimethyl ether. These solvents can be used alone or in combination of two or more.
[0162] The amount of solvent (G) in the adhesive composition is, for example, 200 parts by mass or less, preferably 100 parts by mass or less, more preferably 30 parts by mass or less, and particularly preferably 10 parts by mass or less, relative to a total of 100 parts by mass of the copolymer (A) and monomer (a). Furthermore, the adhesive composition may also substantially not contain solvent (G), for example, the amount of solvent (G) may be 1 part by mass or less or 0 parts by mass relative to a total of 100 parts by mass of the copolymer (A) and monomer (a).
[0163] 1.9 Other Additives (H) The adhesive composition may also include, as needed and without impairing the effects of the present invention, other known additives such as crosslinking accelerators, anti-aging agents, fillers, colorants (pigments, dyes, etc.), ultraviolet absorbers, antioxidants, plasticizers, softeners, surfactants, antistatic agents, and dispersants.
[0164] As the dispersant, conventionally known dispersants can be used. The acid value of the dispersant is preferably 150 mg KOH / g or less, but the lower limit is not particularly limited; it can be 5 mg KOH / g or more, 6 mg KOH / g or more, or 7 mg KOH / g or more. The dispersant preferably has a polyoxyalkylene glycol group. Examples of dispersants include: Disperbyk-102, Disperbyk-111, Disperbyk-190, Disperbyk-191, Disperbyk-194N, Disperbyk-2010, Disperbyk-2012, and Disperbyk-2015 manufactured by BYK-Chemie Japan Co., Ltd.; TEGO Dispers-715W, TEGO Dispers-750W, and TEGO Dispers-755W manufactured by Evonik Japan Co., Ltd.; and Efka6230 manufactured by BASF.
[0165] The content of the dispersant is not particularly limited, but is, for example, 0 to 30 parts by mass relative to 100 parts by mass of inorganic particles (B), preferably 1 to 15 parts by mass, and more preferably 3 to 10 parts by mass.
[0166] 2. Adhesive layer / laminate An adhesive layer is formed by a process of applying the adhesive composition to a suitable substrate and a process of curing (preferably photocuring) the coating layer obtained by the coating process to form an adhesive layer.
[0167] The substrate is not particularly limited and can be a release film or a component for which adhesion is desired (e.g., an optical film or other optical component). By using an optical component (e.g., an optical film) as the substrate, optical components (e.g., optical films) with laminated adhesive (adhesive layers) can be manufactured. Furthermore, by using a release film as the substrate, adhesive (adhesive layers) can be transferred to various components. As a result, components with laminated adhesive (adhesive layers) (e.g., optical films or other optical components) can be manufactured.
[0168] As a release film, conventionally known release films can be used, but plastic films are preferred in terms of cost and superior surface smoothness.
[0169] During the curing process in the adhesive layer formation step, it is preferable to irradiate the coating layer obtained through the coating step with active energy rays. Examples of such active energy rays include ultraviolet light, lasers, alpha rays, beta rays, gamma rays, X-rays, and electron beams. From the viewpoints of controllability, operability, and cost, ultraviolet light is preferred. More preferably, ultraviolet light with a wavelength of 200 nm or more and 400 nm or less is used. Ultraviolet light can be irradiated using light sources such as high-pressure mercury lamps, microwave-excited lamps, chemical lamps, black lights, LEDs, and metal halide lamps.
[0170] The curing is preferably carried out under a nitrogen atmosphere and / or with a release film laminated coating layer.
[0171] This method enables the manufacture of a laminate comprising a substrate and an adhesive layer laminated on the substrate. Such a laminate is also included in this invention.
[0172] As a laminate containing an adhesive layer formed by the adhesive composition of the present invention, it is acceptable as long as the adhesive layer is laminated on any substrate (e.g., the release film or optical component described above), preferably a laminate in which the adhesive layer is laminated on an optical component such as an optical film.
[0173] It should be noted that, as long as the substrate and the adhesive layer are directly laminated, other components can be laminated on the surface of the substrate where the adhesive layer is not laminated and on the surface of the substrate where the adhesive layer is not laminated.
[0174] Furthermore, the adhesive layer formed in this manner comprises a copolymer (A) and inorganic particles (B). The copolymer (A) in the adhesive layer is a copolymer (A) comprising aromatic structural units (A1) and hydroxyl-containing structural units (A2), and Preferably, the content of the structural unit (A2) is 1 to 40% by mass of the copolymer (A) in 100% by mass of the copolymer (A) (preferably in the total of 100% by mass of the structural unit (A1) and the structural unit (A2), which is the same as the copolymer (A) in the adhesive composition.
[0175] Hereinafter, the adhesive layer comprising a copolymer (A) and inorganic particles (B), wherein the copolymer (A) comprises structural units (A1) and structural units (A2), and the content of the structural units (A2) is 1 to 40% by mass of 100% by mass of the copolymer (A) (preferably the sum of structural units (A1) and (A2)).
[0176] The copolymer (A) contained in the adhesive layer of the present invention includes structural units (A1), structural units (A2), etc., and may include structural units (A3) as needed (specifically structural units (A31) to (A42)). Specific examples and preferred examples of these structural units are the same as those described above for the copolymer (A). The content of each structural unit in 100% by mass of the copolymer (A) in the adhesive layer of the present invention is as follows, for example.
[0177] The content of structural unit (A1) is, for example, 40 to 99% by mass, preferably 50 to 95% by mass, and more preferably 70 to 90% by mass.
[0178] The content of the structural unit (A2) is, for example, 1 to 40% by mass, preferably 3 to 30% by mass, more preferably 7 to 25% by mass. It can also be 12 to 25% by mass.
[0179] The content of the structural unit (A3) is, for example, 0 to 50% by mass, preferably 1 to 50% by mass, more preferably 1 to 40% by mass, even more preferably 5 to 25% by mass, and particularly preferably 5 to 20% by mass.
[0180] The content of the structural unit (A31) is, for example, 0 to 50% by mass, preferably 5 to 40% by mass, more preferably 10 to 30% by mass, and even more preferably 10 to 20% by mass.
[0181] The content of the structural unit (A32) is, for example, 0 to 50% by mass, preferably 1 to 30% by mass, more preferably 5 to 20% by mass, and even more preferably 5 to 10% by mass.
[0182] The content of the structural unit (A33) is, for example, 0 to 50% by mass, preferably 5 to 40% by mass, and more preferably 10 to 30% by mass.
[0183] The content of the structural unit (A34) is, for example, 0 to 50% by mass, preferably 0 to 30% by mass, and more preferably 1 to 20% by mass.
[0184] The content of the structural unit (A35) is, for example, 0 to 50% by mass, preferably 0 to 10% by mass, and more preferably 0 to 5% by mass.
[0185] The content of the structural unit (A36) is, for example, 0 to 50% by mass, preferably 0 to 30% by mass, more preferably 0 to 10% by mass or 0% by mass.
[0186] The content of the structural unit (A37) is, for example, 0 to 50% by mass, preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.
[0187] The content of the structural unit (A38) is, for example, 0 to 50% by mass, preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.
[0188] The content of the structural unit (A39) is, for example, 0 to 50% by mass, preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.
[0189] The content of the structural unit (A40) is, for example, 0 to 50% by mass, preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.
[0190] The content of the structural unit (A41) is, for example, 0 to 50% by mass, preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.
[0191] The content of the structural unit (A42) is, for example, 0 to 50% by mass, preferably 0 to 20% by mass, and more preferably 0 to 10% by mass.
[0192] The total content of structural unit (A1) and structural unit (A2) in 100% by mass of copolymer (A) in the adhesive layer is, for example, 50-100% by mass, preferably 60-99% by mass, more preferably 75-95% by mass, and may also be 85-100% by mass or 95-100% by mass. Furthermore, the mass ratio (A1 / A2) of structural unit (A1) to structural unit (A2) is, for example, 50 / 50-99 / 1, preferably 70 / 30-98 / 2, more preferably 75 / 25-95 / 5, even more preferably 80 / 20-90 / 10, and particularly preferably 83 / 17-89 / 11.
[0193] The weight-average molecular weight of the copolymer (A) in the adhesive layer of the present invention is, for example, 500,000 to 3,000,000, preferably 700,000 to 2,500,000, more preferably 1,000,000 to 2,000,000, and particularly preferably 1,200,000 to 1,500,000.
[0194] When a photopolymerization initiator is used to cure an adhesive composition to form an adhesive layer, the adhesive layer typically contains photopolymerization initiator residue.
[0195] Relative to 100 parts by weight of copolymer (A), the amount of residual monomer (a) in the adhesive layer of the present invention is, for example, 1 part by weight or less, preferably 0.5 parts by weight or less, and more preferably 0.3 parts by weight or less. By including sufficient monomer (a) in the adhesive composition before curing, and by properly dispersing the inorganic particles (B), this characteristic is maintained even if the monomer (a) decreases in the cured adhesive layer, and high transparency is maintained even if the thickness of the adhesive layer increases.
[0196] The preferred embodiment of the inorganic particles (B) contained in the cured adhesive layer is the same as that described above as the inorganic particles (B) before curing.
[0197] Relative to 100 parts by mass of copolymer (A), the amount of inorganic particles (B) in the adhesive layer of the present invention is, for example, 20 to 2000 parts by mass, preferably 50 to 1500 parts by mass, more preferably 80 to 1000 parts by mass, and can be 80 to 500 parts by mass or 80 to 250 parts by mass. By adjusting the proportion of inorganic particles (B) within the above range, it is easier to balance refractive index and transparency.
[0198] The total content of copolymer (A) and inorganic particles (B) in the adhesive layer of the present invention is preferably 80 to 100% by mass in 100% by mass of the adhesive layer, more preferably 90 to 99.9% by mass, and even more preferably 95 to 99.9% by mass.
[0199] When the thickness of the adhesive layer of the present invention is set to 100µm, the haze is, for example, 3.0% or less, preferably 2.0% or less, and more preferably 1.0% or less.
[0200] The thickness of the adhesive layer of the present invention is not particularly limited, and can be, for example, 1–2000 µm, 30–1000 µm, 50–700 µm, or about 100–500 µm. In particular, because the adhesive layer of the present invention is formed from a specific adhesive composition, it can maintain both transparency and refractive index even when forming thick films (e.g., 50 µm or more, preferably 100 µm or more), making it suitable for bonding optical films. Furthermore, the thickness of the adhesive layer of the present invention can be 2–300 µm, 3–200 µm, or 5–100 µm.
[0201] It should be noted that, regardless of the thickness, the haze of the adhesive layer of the present invention is, for example, 3.0% or less, preferably 2.0% or less, more preferably 1.0% or less, and the lower limit can be about 0.1%.
[0202] Furthermore, since the copolymer (A) constituting the adhesive layer of the present invention contains hydroxyl-containing structural units (A2), the increase in haze is small even when placed under humidified conditions. The haze after the humidification test (temperature 60°C, relative humidity 95%RH, 500 hours) described later is, for example, 13% or less, preferably 10% or less, more preferably 7% or less, even more preferably 5% or less, and the lower limit can be about 1%.
[0203] The refractive index of the adhesive layer of the present invention is, for example, 1.58 to 1.80, preferably 1.60 to 1.75, and more preferably 1.61 to 1.72. If the refractive index of the adhesive layer is within the range described above, it is suitable for bonding optical films.
[0204] The adhesive composition and adhesive layer can be used for various applications, and are preferably used for bonding optical components such as optical films, i.e., for bonding adhesive layers laminated onto optical components such as optical films. Specifically, they are preferably used for bonding optical components such as optical films in image display devices such as liquid crystal displays, organic EL displays, plasma displays (PDPs), micro LED displays, curved displays, and flexible displays. In particular, the adhesive composition and adhesive layer are preferably used for thin adhesive optical films used in large liquid crystal panels.
[0205] Examples of optical films include: polarizing plates, phase retardation plates for color correction prevention, optical compensation films such as viewing angle expansion films for improving the viewing angle of liquid crystal displays, brightness enhancement films for improving the contrast of displays, light extraction films for improving the light extraction efficiency of surface light emitters, and optical films formed by stacking these films.
[0206] This application claims priority based on Japanese Patent Application No. 2024-064673, filed April 12, 2024; Japanese Patent Application No. 2024-082136, filed May 20, 2024; and Japanese Patent Application No. 2024-179870, filed October 15, 2024. The entire contents of the descriptions of Japanese Patent Application No. 2024-064673, filed April 12, 2024; Japanese Patent Application No. 2024-082136, filed May 20, 2024; and Japanese Patent Application No. 2024-179870, filed October 15, 2024, are incorporated herein by reference.
[0207] Example The present invention will be described in more detail below with examples, but the present invention is of course not limited to the following examples, and can certainly be implemented by appropriate modifications within the scope suitable for the above and following spirit, all of which are included within the technical scope of the present invention. It should be noted that in the following description, "parts" refers to "parts by mass". In addition, unless otherwise specified, the operation and physical properties, etc., are measured under the conditions of room temperature 23°C and relative humidity 55%RH.
[0208] 1. Measurement Method 1.1 Weight-average molecular weight (Mw) The weight-average molecular weight (Mw) of the (meth)acrylate copolymer (A) was determined by GPC (gel permeation chromatography) under the following conditions: Analytical device: HLC-8120GPC manufactured by Tosoh Corporation; Column: Made by Tosoh Co., Ltd., G7000HXL+GMHXL+GMHXL; Column dimensions: 7.8mm φ × 30cm each, totaling 90cm; Column temperature: 40℃; Flow rate: 0.8 ml / min; Injection volume: 100µl; Eluent: Tetrahydrofuran; Detector: Differential refractometer (RI); Standard sample: polystyrene.
[0209] 1.2 Amount of (meth)acrylate monomer (a) The residual amount and composition of (meth)acrylate monomers (a) were determined using GC / MS (GC-Agilent GC7980A, MS-Nippon Electron Ltd. Q-1050GC).
[0210] 1.3 Composition of copolymer (A) The composition of the copolymer was determined by NMR. The NMR peaks of the copolymer components were assigned with reference to the "Aldrich Library of NMR Spectra" and the "13C-NMR Spectra" of Sadtler Research Lab. Furthermore, the copolymer composition was determined using... 1 H and 13 The integral value of C is used for calculation. It should be noted that the measuring apparatus used is JNM-GX400 (manufactured by Nippon Electron Ltd.), the solvent used is deuterated chloroform, and the measuring temperature is 27°C.
[0211] 1.4 refractive index The refractive index of the adhesive layer (thickness: 20µm) obtained in the examples or comparative examples was determined using an Abbe refractometer at 25°C as a value relative to the sodium D line.
[0212] 1.5 haze Peel off one side of the PET film from the adhesive layer (thickness: 100µm) sandwiched between PET films obtained in the examples or comparative examples, and roll-press the exposed adhesive surface onto alkali-free glass (82mm × 53mm × 0.5mm thickness). Next, peel off the other side of the PET film and roll-press it onto alkali-free glass (82mm × 53mm × 0.5mm thickness). Then, perform autoclaving treatment (50°C, gauge pressure 0.4MP, 20 minutes) for fine lamination to produce an evaluation sample.
[0213] The haze of the obtained evaluation samples was measured using a haze meter (NDH5000, manufactured by Nippon Denshoku Kogyo Co., Ltd.) according to JIS K7136 (2000) at an environment of 25°C and 55%RH.
[0214] 1.6 Durability (Heating Test, Humidification Test, HS Test) An organic EL display device with an optical compensation layer, having an adhesive layer (thickness: 20µm) prepared as described below, was manufactured as a sample for durability evaluation. The obtained samples were subjected to the following tests, and their appearance was visually inspected and evaluated according to the following criteria.
[0215] (1) Treated at 85℃ for 500 hours (heating test); (2) Treated for 500 hours at a temperature of 60℃ and a relative humidity of 95%RH (humidification test); (3) Place the product in an environment of 85°C for 30 minutes and then place it in an environment of -40°C for 30 minutes as one cycle. Perform 300 cycles (300 hours) of treatment with one cycle of 1 hour each (thermal shock (HS) test).
[0216] -Evaluation Criteria- ◎: The end is completely free of air bubbles; ○: There are a few air bubbles at the end, but this is not a problem in actual application; Δ: There are air bubbles at the end, but this is not a problem in practical applications unless there is a special purpose. ×: There are a significant number of air bubbles at the end, which poses a problem in practical applications.
[0217] 1.7 Haze (%) after humidification test The samples used for the above-mentioned durability humidification test were taken out at room temperature (23°C, 55%RH) and left to stand for 3 hours. Then, the haze was measured using a haze meter (Nippon Denshoku Kogyo Co., Ltd., NDH5000) according to JIS K7136 (2000) at a temperature of 25°C and a relative humidity of 55%RH.
[0218] 1.8 Coating properties Immediately after forming the adhesive layer (thickness: 20µm) of the examples or comparative examples, the surface condition of the adhesive layer was visually inspected and evaluated according to the following criteria. In the five-stage evaluation, 5 is the best, and 3 or above indicates practical applicability.
[0219] 5: No streaks or uneven coating; 4: Some areas may have slight streaks or uneven application. 3: Slight streaks or uneven application are present on the entire surface; 2: Severe coating streaks or severe uneven coating exist on parts or the entire surface; 1: Unable to form a uniform coating surface.
[0220] 2. Preparation of (meth)acrylate copolymer (A) [Manufacturing Examples 1-13, 19-21, 26-31] Inside a reaction chamber isolated from external ultraviolet light, four black light lamps (Sankyo Electric Co., Ltd. FL20SBL) serving as UV lamps were placed at the four corners. A 2L four-necked flask equipped with a stirrer, thermometer, nitrogen inlet pipe, and cooling pipe was placed inside the reaction chamber. Aromatic monomers (a1), hydroxyl-containing monomers (a2), and other monomers (a3) were added to the flask according to the amounts shown in Tables 1-3. The flask was heated to 30°C while purging the air inside with nitrogen. Next, the photopolymerization initiator was added while stirring according to the amounts shown in Tables 1-3, and the mixture was thoroughly mixed.
[0221] To initiate polymerization, ultraviolet light (cumulative light intensity 200 mJ / cm²) was used to illuminate the material using a black light lamp. 2 After the reaction started, the reaction was stopped by introducing air into the flask using an air pump when the reaction temperature rose by 10°C, resulting in acrylic slurries containing (meth)acrylate copolymers (A-1) to (A-13), (A-19) to (A-21), and (A-26) to (A-31). The characteristics of the copolymers (A) and residual monomers (a) in the acrylic slurries are shown in Tables 1 to 3.
[0222] [Manufacturing Examples 14 to 18] In a four-necked flask equipped with a stirring blade, thermometer, nitrogen inlet pipe, and cooler, aromatic monomers (a1), hydroxyl-containing monomers (a2), other monomers (a3), and a thermal polymerization initiator were added according to the amounts shown in Table 2. Nitrogen gas was introduced while stirring slowly. After nitrogen purging, the liquid temperature in the flask was controlled at around 60°C, and the polymerization reaction was carried out for 0.5 hours to prepare acrylic slurries containing (meth)acrylate copolymers (A-14) to (A-18). The characteristics of the copolymers (A) and residual monomers (a) in the acrylic slurries are shown in Table 2.
[0223] [Manufacturing Examples 22-25] In a four-necked flask equipped with a stirring blade, thermometer, nitrogen inlet pipe, and cooler, aromatic monomers (a1), hydroxyl-containing monomers (a2), other monomers (a3), and thermal polymerization initiator were added according to the amounts shown in Table 3. 100 parts by weight of ethyl acetate were also added, and nitrogen was introduced while stirring slowly. After nitrogen purging, the liquid temperature in the flask was controlled at around 80°C, and the polymerization reaction was carried out for 2 hours to prepare solutions of (meth)acrylate copolymers (A-22) to (A-25). The characteristics of the copolymers (A) and residual monomers (a) in the solutions are shown in Table 3.
[0224]
[0225]
[0226]
[0227]
[0228]
[0229]
[0230] The meanings of the symbols in Tables 1 to 3 are as follows.
[0231] A-BPML: p-Phenylenyl acrylate (manufactured by Shin-Nakamura Chemical Industry Co., Ltd.); NMT-A: Naphthylmethyl acrylate (manufactured by Kyoeisha Chemical Co., Ltd.); A-LEN-10: Ethoxylated o-phenylphenol acrylate (A-LEN-10, manufactured by Shin-Nakamura Chemical Industry Co., Ltd.). POB-A: Light Acrylate POB-A (manufactured by Kyoei Chemical Co., Ltd.). PhEA: Phenoxyethyl acrylate (manufactured by Kyoeisha Chemical Co., Ltd.); BzA: Benzyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd.). 4HBA: 4-hydroxybutyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd.). HEAA: N-hydroxyethylacrylamide (manufactured by KJ Chemicals Co., Ltd.); IBXA: Isoborneol acrylate (manufactured by Nippon Shokubai Co., Ltd.). ACMO (registered trademark): N-acryloylmorpholine (manufactured by KJ Chemicals Co., Ltd.); BA: n-butyl acrylate (manufactured by Nippon Shokubai Co., Ltd.); 2EHA: 2-Ethylhexyl acrylate (manufactured by Nippon Shokubai Co., Ltd.); MEA: Ethyl methoxyacrylate (manufactured by Nippon Shokubai Co., Ltd.). AA: Acrylic acid (Nippon Shokubai Co., Ltd.); Omnirad (registered trademark) 651: 2,2-dimethoxy-1,2-diphenylethane-1-one (manufactured by IGM Resins BV). AIBN: 2,2'-Azobisisobutyronitrile (manufactured by Fujifilm and Waku Pure Chemical Industries, Ltd.)
[0232] 3. Preparation of adhesive composition [Examples 1 to 24, Comparative Examples 1 to 13] The slurry of (meth)acrylate copolymer (A) obtained in Manufacturing Examples 1 to 31 (wherein the amount of solid components in the slurry, i.e., the total amount of (meth)acrylate copolymer (A) and residual monomer (a) in the slurry is 100 parts by mass) or the solution of (meth)acrylate copolymer (A) (wherein the amount of solid components in the solution, i.e., the total amount of (meth)acrylate copolymer (A) and residual monomer (a) in the solution is 100 parts by mass) is mixed with the inorganic particles (B) (converted amount of zirconia particles), silane coupling agent (C), crosslinking agent (D) (converted amount of active ingredient), additional monomer (a), photopolymerization initiator (E) and chain transfer agent (F) shown in Tables 4 to 6, and degassing treatment is performed to prepare an adhesive composition.
[0233] 4. Preparation of the adhesive layer [Examples 1 to 24, Comparative Examples 8 to 13] The obtained adhesive composition was applied to the release-treated side of a 75µm thick polyethylene terephthalate (PET) film that had undergone single-sided release treatment (silicone treatment) to achieve the specified coating thickness (target adhesive layer thickness). The release-treated side of the 75µm thick PET film was then laminated onto the coated surface, thereby positioning the PET film on both sides of the adhesive composition and sealing it as a sandwich structure. The mixture was then irradiated from above and below with a black light at a intensity of 2.0 mW / cm². 2 (Cumulative light intensity: 400 mJ / cm² at the top and bottom) 2 ), to obtain the adhesive layer.
[0234] [Comparative Examples 1 to 7] The obtained adhesive composition was applied to the release-treated surface of a 75µm thick polyethylene terephthalate (PET) film after release treatment (silicone treatment) in such a manner that the thickness of the heat-treated coating was equal to the target adhesive layer thickness. Then, it was heat-treated at 120°C for 2 minutes to form the coating. It should be noted that the heat treatment was performed by a floating drying method using hot air blown directly from above and below the film. Then, the release-treated surface of the 75µm thick PET film after release treatment was adhered to the dried coating surface, thereby placing the PET films on the top and bottom of the coating and sealing them in a sandwich shape. A black light of 2.0 mW / cm² was used to irradiate the coating from above and below. 2 (Cumulative light intensity: 400 mJ / cm² at the top and bottom) 2 ), to obtain the adhesive layer.
[0235] The properties of the obtained adhesive layer were evaluated. The results are shown in Tables 4 to 6.
[0236]
[0237]
[0238]
[0239] The meanings of the symbols in Tables 4 to 6 are as follows.
[0240] [HR-LP-3-1]: Zirconia microparticle dispersion (Nippon Shokubai Ltd. (specific manufacturing method shown in "Manufacturing of Zirconia Microparticles (HR-LP-3-1)" below), volume average particle size 18 nm, particle refractive index 1.86, dispersion of monomer POBA (phenoxybenzyl acrylate), solid content concentration 85% by mass). [KBM-403]: 3-glycidoxypropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd.); [A-DPH]: Dipentaerythritol polyacrylate (manufactured by Shin-Nakamura Chemical Industry Co., Ltd., a mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate). [POBA(1)]: phenoxybenzyl acrylate derived from HR-LP-3-1; [POBA(2)]: Phenoxybenzyl acrylate (manufactured by Kyoei Chemical Co., Ltd., Light Acrylate POB-A); [POBA Total]: Total of phenoxybenzyl acrylate (total of POBA(1) and POBA(2)); [Omnirad (registered trademark) 184]: 1-Hydroxycyclohexylphenyl ketone (manufactured by IGM Resins BV); [EHMP]: 2-Ethylhexyl 3-mercaptopropionic acid (manufactured by SC Organic Chemicals Co., Ltd.).
[0241] [Manufacturing of Zirconia Particles (HR-LP-3-1)] A solution of 2-ethylhexanoate zirconium mineral oil (782 parts, zirconium content 44% by mass) was mixed with pure water (268 parts). The resulting mixture was placed in an autoclave equipped with a stirrer, and the atmosphere inside the autoclave was purged with nitrogen. The mixture was then heated to 210°C and maintained at this temperature for 16 hours to produce zirconium oxide (zirconia) particles. The reacted mixture was then removed, filtered, and the precipitate accumulated at the bottom was separated. The precipitate was washed with acetone and dried. The dried precipitate (100 parts) was dispersed in toluene (700 parts) to obtain a cloudy white solution. As a purification step, the solution was filtered again using quantitative filter paper (Advantech Toyo Co., Ltd., No. 5C) to remove coarse particles from the precipitate. The filtrate was then concentrated under reduced pressure to remove toluene and recover the white zirconium oxide particles.
[0242] It should be noted that the number-average particle size of the recovered zirconia microparticles was determined by observation using an ultra-high resolution electrolytic emission scanning electron microscope (Hitachi High Technology Co., Ltd., S-4800). The zirconia microparticles were observed at 150,000x magnification, and the length of the major axis of any random group of 100 particles was measured; the average value of these measurements was taken as the number-average particle size. The number-average particle size of the zirconia microparticles obtained by electron microscopy was 18 nm.
[0243] The zirconia microparticles obtained above, phenoxybenzyl acrylate (manufactured by Kyoeisha Chemical Co., Ltd., LightAcrylate POB-A), and DISPER BYK-111 (manufactured by BYK Chemie Japan Co., Ltd.) were mixed / stirred at a mass ratio of zirconia microparticles / phenoxybenzyl acrylate / BYK-111 = 80.0 / 15.0 / 5.0 to prepare a zirconia microparticle dispersion (HR-LP-3-1). It should be noted that the volume average particle size of the zirconia microparticles in the obtained dispersion is 18 nm, and the particle refractive index is 1.86.
[0244] It should be noted that the organic EL display device manufactured in the following manner was used in the durability evaluation and haze evaluation after humidification test.
[0245] 5. Organic EL display device 5.1 Fabrication of Polarizing Plate Prepare an A-PET (amorphous polyethylene terephthalate) film (manufactured by Mitsubishi Chemical Corporation, trade name: Novaclear (registered trademark) SH046, thickness 200µm) as the substrate, and perform corona treatment on the surface (corona discharge amount 58W). min / m 2 Additionally, polyvinyl alcohol (PVA) with 1% by mass of acetylacetyl-modified polyvinyl alcohol (manufactured by Mitsubishi Chemical Corporation, trade name: Gohsefimer (trademark) Z200, degree of polymerization 1200, degree of saponification ≥99.0%, degree of acetylacetyl modification 4.6%) was prepared. This PVA was coated onto the corona-treated surface of an A-PET film with a dried film thickness of 12µm, and dried using hot air at 60°C for 10 minutes. In this manner, a laminate with a polyvinyl alcohol (PVA) resin layer disposed on a substrate was formed.
[0246] Next, the laminate was first stretched to 2.0 times its original size in air at 130°C to obtain an extended laminate. Then, the extended laminate was immersed in a boric acid-insoluble aqueous solution at 30°C for 30 seconds to insolublee the PVA-based resin layer containing oriented polyvinyl alcohol molecules. This boric acid-insoluble aqueous solution was obtained with a boric acid content of 3% by mass relative to 100% by mass of water. The extended laminate was then dyed to generate a colored laminate. The colored laminate was obtained by immersing the extended laminate in a dyeing solution containing iodine and potassium iodide at 30°C, causing the PVA-based resin layer in the extended laminate to adsorb iodine. The iodine concentration and immersion time were adjusted so that the monomer transmittance of the resulting polarizer was 44.5%. Specifically, the staining solution uses water as a solvent, with an iodine concentration between 0.08% by mass and 0.25% by mass, and a potassium iodide concentration between 0.56% by mass and 1.75% by mass. The iodine to potassium iodide concentration ratio is 1:7.
[0247] Next, a crosslinking process is performed on the PVA molecules of the iodine-adsorbed PVA-based resin layer by immersing the colored laminate in a boric acid crosslinking aqueous solution at 30°C for 60 seconds. In this process, the boric acid content in the boric acid crosslinking aqueous solution is set to 3% by mass relative to 100% by mass of water, and the potassium iodide content is set to 3% by mass relative to 100% by mass of water. Furthermore, the resulting colored laminate is stretched in the boric acid aqueous solution at a stretching temperature of 70°C in the same direction as the stretching in air described above, to a length of 2.7 times, and the final stretching ratio is set to 5.4 times, resulting in a substrate / polarizer laminate. The polarizer thickness is 5µm. In this process, the boric acid content in the boric acid crosslinking aqueous solution is set to 6.5% by mass relative to 100% by mass of water, and the potassium iodide content is set to 5% by mass relative to 100% by mass of water. The resulting laminate is removed from the boric acid aqueous solution, and the boric acid adhering to the surface of the polarizer is washed with an aqueous solution containing 2% by mass of potassium iodide relative to 100% by mass of water. The cleaned laminate was dried with hot air at 60°C.
[0248] On the surface of the polarizer in the aforementioned substrate / polarizer laminate, an acrylic film with a thickness of 40µm is bonded using a PVA-based adhesive. This yields a polarizing plate comprising a protective layer / polarizer / resin substrate.
[0249] 5.2 Fabrication of the liquid crystal alignment and curing layer constituting the first optical compensation layer According to the process described in paragraphs
[0151] to
[0156] of Japanese Patent Application Publication No. 2006-133652, a liquid crystal alignment curing layer (first optical compensation layer) is formed on a substrate (TAC film). It should be noted that the direction of the rubbing treatment is set to be 15° counterclockwise relative to the absorption axis of the polarizer when viewed from the visible side after bonding with the polarizer. The thickness of the first optical compensation layer is 1.7µm, and the in-plane phase difference Re(550) is 270nm. Furthermore, the first optical compensation layer is a negative A-type plate exhibiting refractive index characteristics of nx=nz>ny. In addition, no protrusions with a height of 0.4µm or more were found on the surface of the first optical compensation layer (negative A-type plate).
[0250] 5.3 Fabrication of the liquid crystal alignment curing layer constituting the second optical compensation layer A liquid crystal composition (coating solution) was prepared by dissolving 10g of a polymerizable liquid crystal compound (manufactured by BASF, trade name "Paliocolor LC242") that displays a nematic liquid crystal phase and 3g of a photopolymerization initiator for the polymerizable liquid crystal compound (Omnirad 907; manufactured by IGM Resins BV) in 40g of toluene.
[0251] A photoalignment film was coated onto the surface of a polyethylene terephthalate (PET) film (38 µm thick) to perform a photoalignment treatment. The direction of the photoalignment treatment was set so that, when viewed from the visible side with a polarizer, it was 75° counterclockwise relative to the absorption axis of the polarizer. The aforementioned liquid crystal composition was then coated onto the photoaligned surface using a bar coater and dried at 90°C for 2 minutes, thereby aligning the liquid crystal compound. The liquid crystal layer formed in this manner was then irradiated with a metal halide lamp at 1 mJ / cm². 2 The light is used to cure the liquid crystal layer, thereby forming a liquid crystal alignment and curing layer (second optical compensation layer) on the substrate (PET film). The thickness of the second optical compensation layer is 1.2µm, and the in-plane phase difference Re(550) is 140nm. Furthermore, the second optical compensation layer is a positive A-type plate exhibiting refractive index characteristics of nx>ny=nz.
[0252] 5.4 Fabrication of a polarizing plate with an optical compensation layer The A-PET film of the substrate is peeled off from the polarizing plate obtained above, and the first optical compensation layer is transferred from the substrate / first optical compensation layer laminate to the peeling surface using a UV-curable adhesive. Then, the second optical compensation layer is transferred from the substrate / second optical compensation layer laminate to the surface of the first optical compensation layer using a UV-curable adhesive. In this way, a polarizing plate with an optical compensation layer is obtained, consisting of a protective layer / polarizer / first optical compensation layer (negative A-type plate: λ / 2 plate) / second optical compensation layer (positive A-type plate: λ / 4 plate).
[0253] 5.5 Fabrication of a polarizing plate with adhesive layer and optical compensation layer On the polarizing plate side (opposite to the protective film side) where the adhesive layer is to be formed on the polarizing plate with the optical compensation layer obtained above, a corona discharge of 80W is applied. min / m 2 A corona treatment is performed to form an easy-to-adhere layer. Then, the PET film with the adhesive layer is laminated in such a way that the formed easy-to-adhere layer is in contact with the adhesive layer (thickness: 20µm) obtained in the example or comparative example to produce a polarizing plate with an adhesive layer and an optical compensation layer.
[0254] 5.6 Fabrication of Organic EL Display Devices Cut the obtained polarizing plate with adhesive and optical compensation layers into 100mm x 50mm dimensions. Disassemble a Samsung Electronics Corporation smartphone (Galaxy-S23) and remove the organic EL display device. Peel off the polarizing film attached to the organic EL display device and replace it with the cut polarizing plate with optical compensation layer to obtain the organic EL display device.
[0255] Industrial availability The adhesive composition and adhesive layer of the present invention can be used in various components, and are preferably used for bonding and adhesion of optical films.
Claims
1. An adhesive composition for optical films, comprising a (meth)acrylate copolymer (A), a (meth)acrylate monomer (a), and inorganic particles (B), The copolymer (A) comprises structural units (A1) derived from an aromatic hydrocarbon-containing (meth)acrylate monomer (a1) and structural units (A2) derived from a hydroxyl-containing (meth)acrylate monomer (a2). The monomer (a) comprises an aromatic hydrocarbon-containing (meth)acrylate monomer (a1) and a hydroxyl-containing (meth)acrylate monomer (a2). The content of the structural unit (A2) is 1-40% by mass of 100% by mass of the copolymer (A). The content of the monomer (a) is 45 to 95% by mass of the total 100% mass of the copolymer (A) and the monomer (a).
2. The adhesive composition according to claim 1, wherein, The adhesive composition further contains a photopolymerization initiator (E).
3. The adhesive composition according to claim 1, wherein, The monomer (a1) is at least one selected from the group consisting of aryl esters of (meth)acrylic acid, aralkyl esters of (meth)acrylic acid, and aryloxyalkyl esters of (meth)acrylic acid. The aryl esters, aralkyl esters, and aryloxyalkyl esters of (meth)acrylic acid are optionally bonded with aryl, aralkyl, aroxy, or aroxyalkyl groups. The aryl esters, aralkyl esters, and aryloxyalkyl esters of (meth)acrylic acid are optionally epoxide-modified.
4. The adhesive composition according to claim 1, wherein, The copolymer (A) comprises structural units (A3) derived from monomers other than aromatic hydrocarbon-containing (meth)acrylate monomers (a1) and hydroxyl-containing (meth)acrylate monomers (a2). The (meth)acrylate monomer (a) comprises monomers (a3) other than the (meth)acrylate monomer (a1) containing an aromatic hydrocarbon group and the (meth)acrylate monomer (a2) containing a hydroxyl group. The content of the structural unit (A3) is less than 50% by mass of 100% by mass of the copolymer (A).
5. The adhesive composition according to claim 4, wherein, The other monomers (a3) comprise at least one selected from the group consisting of (meth)acrylate monomers containing alicyclic hydrocarbon groups, (meth)acrylate monomers containing nitrogen atoms, (meth)acrylate monomers containing alkoxyalkyl groups, low Tg (meth)acrylate alkyl monomers with a glass transition temperature of less than -20°C for homopolymers, and monomers containing acid groups.
6. The adhesive composition according to claim 1, wherein, The copolymer (A) has a weight-average molecular weight of 500,000 to 6,000,000.
7. The adhesive composition according to claim 1, wherein, The inorganic particles (B) are particles composed of at least one selected from the group consisting of alumina, titanium oxide, zirconium oxide, indium oxide, zinc oxide, tin oxide, lanthanum oxide, yttrium oxide, cerium oxide, magnesium oxide, niobium oxide, tantalum oxide, indium tin oxide, antimony tin oxide, barium titanate, strontium titanate, perovskite, and spinel.
8. The adhesive composition according to claim 1, wherein, The volume average particle size of the inorganic particles (B) is 1–100 nm.
9. The adhesive composition according to claim 1, wherein, In the particle size determination of the inorganic particles (B) based on dynamic light scattering, the ratio (D90 / D50) of the cumulative 90% particle size of the volume reference to the cumulative 50% particle size of the volume reference is less than 3.
0.
10. The adhesive composition according to claim 1, wherein, The adhesive composition further contains a chain transfer agent (F).
11. The adhesive composition according to claim 1, wherein, The refractive index of the adhesive layer formed from the adhesive composition is 1.58 to 1.
80.
12. The adhesive composition according to claim 1, wherein, The haze of an adhesive layer with a thickness of 100µm formed from the adhesive composition is less than 3.0%.
13. An adhesive layer formed from an adhesive composition according to any one of claims 1 to 12.
14. Use of a composition in an adhesive laminated on an optical film, said composition being the composition according to any one of claims 1 to 12.
15. A laminate comprising an optical film and an adhesive layer according to claim 13 laminated on the optical film.
16. A method for manufacturing an optical film laminated with an adhesive, comprising: The process of applying the composition according to any one of claims 1 to 12 to a substrate; as well as The process of curing the coating layer obtained in the coating process to form an adhesive layer. The substrate used in the coating process is an optical film, or the process may further include a transfer process after the adhesive layer formation process to transfer the adhesive layer to the optical film.
17. An adhesive layer comprising an (meth)acrylate copolymer (A) and inorganic particles (B) for use in optical films. The thickness of the adhesive layer is 50µm or more. The haze of the adhesive layer is below 3.0%. The copolymer (A) comprises structural units (A1) derived from an aromatic hydrocarbon-containing (meth)acrylate monomer (a1) and structural units (A2) derived from a hydroxyl-containing (meth)acrylate monomer (a2). The content of the structural unit (A2) is 1 to 40% of the total 100% mass of structural units (A1) and (A2).
18. The adhesive layer according to claim 17, wherein, The adhesive layer contains photopolymerization initiator residues.
Citation Information
Patent Citations
Retardation plate, polarizing plate and liquid crystal display
JP2006133652A
Adhesive composition, adhesive and adhesive sheet
JP2017128732A
Server and method
JP2024064673A
Amorphous aluminosilicate particle powder and method for producing the same
JP2024082136A
Unmanned conveyance system and unmanned conveyance method
JP2024179870A